Sesamol-loaded PLGA nanoparticles attenuate HFD-induced MASLD by modulating Nrf2/HO-1, mitochondria cascade, and TLR4/NF-κB signaling pathways in rats - Elsayed S.I. Mohammed; Mohamed Shawky El Sayed; Tahani Ahmad Al-Matrafi; Roshmon ‎Thomas Mathew; Mohamed Ashour; Mohammed Tariq Saud Albaloushi; Hailah M. Almohaimeed; El-Sayed Hemdan Eissa; Sameh A. Abdelnour (Tissue and Cell, 2027)

Histochemical and ultrastructural characterization of the gills in tiger shark, Galeocerdo cuvier (Péron & Lesueur, 1822): Structural strategies for functional adaptation - Fatma A. Madkour; Elsayed S.I. Mohammed; Mohammed Al-Rasheed; Eman E. El-Nahass; Mona M. Elwan; Mohamed Ashour; Roshmon Thomas Mathew; Fatma Abdelhakeem (Tissue and Cell, 2027)

Holocene development and climatic sensitivity of an Amazonian peatland pole forest: Nueva York, Peru - Christine M. Åkesson; Katherine H. Roucoux; Arnoud Boom; Greta C. Dargie; Jhon del Aguila-Pasquel; Gerardo Flores; Pauline Gulliver; William Hiles; Timothy R. Baker; Frederick C. Draper; Adam Hastie; Eurídice N. Honorio Coronado; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Seed bio-priming with multifaceted PGPR from underutilized medicinal plants enhances disease resistance and improves yield in rice - S. Raghu; B. Jeevan; Devayani Sarmah; Mathew Baite; C. Anilkumar; Rupak Jena; M. K. Bag; B. S. Satapathy; S. D. Mohapatra (Australasian Plant Pathology, 2026)

Metabolomic alterations in marine mussels exposed to wastewater, stormwater, and environmental conditions - Jessica Clemens; Maya Faber; Hayley M. Mathews; C. Andrew James (Marine Pollution Bulletin, 2026)

Isolation and antimicrobial characterisation of a new biflavonoid glycoside from the leaves of Campylospermum reticulatum - Baleba Mbanga Moise Roger; Angélique Nicolas Messi; Denis-Gregoire Téné; Gabriel N. Medoua; Mathew M. Nindi; Anastasie Ewola Tih; Raphael Tih Ghogomu (Biochemical Systematics and Ecology, 2026)

Diversity, Functional Guilds, and Seasonal Variation of Spider Assemblages in Coastal Wetlands of Kerala, India - Anitha Abraham; Mathew M. Joseph (Wetlands, 2026)

Connecting ambient toxicity testing with community-level responses of benthic macroinvertebrates in an impacted stream in East Tennessee, USA - Louise M. Stevenson; Paul G. Matson; Peyton C. Marcum; Nikki J. Jones; Scott C. Brooks; Trystan Bordeau; Allison M. Fortner; Natalie A. Griffiths; Christopher R. DeRolph; R. Trent Jett; Michael W. Jones; Peijia Ku; et al. (Journal of Environmental Management, 2026)

Dietary yeast-derived nucleotides enhance reproductive efficiency, blood metabolic profile, antioxidant status, and immune function in rabbit does - Noura H. Gouda; Sameh A. Abdelnour; Elsayed S. I. Mohammed; Mohamed Shawky El Sayed; Mohamed Ashour; Roshmon Thomas Mathew; Mohammed Tariq Saud Albaloushi; Hailah M. Almohaimeed; Ehab El-Haroun; Mahmoud S. Abd-Allah (Veterinary Research Communications, 2026)

Use of translational fusions to express functional Klebsiella oxytoca dinitrogenase reductase in plant mitochondria - Shoko Okada; Xueqin Wang; Christina M. Gregg; Robert S. Allen; Timothy Rhodes; Vanessa Gillespie; Ingrid Venables; Anu Mathew; Jessica K. Bilyj; Keren Byrne; Robert C. DeFeyter; Trevor D. Rapson; et al. (Plant Molecular Biology, 2026)
Engineering crop plants with the biological nitrogen fixation pathway is a longstanding goal of modern agriculture. Dinitrogenase reductase (NifH) is a critical component of the biological nitrogen fixation pathway, with multiple roles in metal cofactor assembly and catalysis. This enzyme must be folded correctly as a soluble homodimer and loaded with the [4Fe-4S] metallocluster for function. Previous studies have found that Klebsiella oxytoca ( Ko ) and Azotobacter vinelandii ( Av ) NifHs were mostly insoluble when targeted to plant mitochondria. Here we found that a translational fusion of two Ko NifH or Av NifH monomers, forming Ko NifHH or Av NifHH synthetic dimers, produced a soluble protein when targeted to plant mitochondria and co-expressed with the putative peptidyl-prolyl cis–trans isomerase NifM. Ko NifHH isolated after expression in leaf mitochondria at ambient oxygen showed some acetylene reduction activity, which did not require co-expression of the nitrogenase-specific metallocluster machinery NifS and NifU. This activity increased after iron-sulfur cluster reconstitution in vitro with recombinant NifU. In a parallel study, we tested a translational fusion of a variant iron-only dinitrogenase reductase ( Av AnfHv6) monomer that was soluble but not active as-isolated from plant mitochondria ( Av AnfHHv6) (Gregg et al. 2025a). Av AnfHHv6 was abundant and fully soluble when isolated from plant mitochondria, like its monomer. Av AnfHHv6 was not active as-isolated but could be largely activated by iron-sulfur cluster reconstitution in vitro. This study demonstrates how translational fusions help improve solubility and have the potential to generate an active NifH enzyme within plant mitochondria.

Seaweed Liquid Extract Improves Growth, Immunity, and Gene Expression in Nile Tilapia (Oreochromis niloticus) - Mohamed Ashour; Einar Ringø; Fawzia S. Ali; Ahmed Mamoon; Othman F. Abdelzaher; Roshmon Thomas Mathew; Abdallah Tageldein Mansour; Yousef Ahmed Alkhamis; Elsayed S. I. Mohammed; Hesham S. Hassanien; Mohamed A. Elokaby; Mohamed M. Mabrouk (Journal of Applied Phycology, 2026)

Efficacy of dietary Artemisia annua against chronic carbendazim exposure in Nile tilapia: growth, antioxidant capacity, intestinal morphology, inflammatory/apoptotic genes - Rowida E. Ibrahim; Abdallah Tageldein Mansour; Ahmed Saud Alsaqufi; Yousef Ahmed Alkhamis; Mohamed Ashour; Roshmon Thomas Mathew; Tarek Khamis; Afaf N. Abdel Rahman; Abdelhakeem El-Murr; Mai A. M. El-son (Aquaculture International, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Phytochemical constituents and antioxidant activity of critically endangered Ophiorrhiza radicans Gardn. (Rubiaceae: Ophiorrhizeae) from Southern Western Ghats, Kerala, India - Jinu Mathew; B. Sruthy; Mity Thambi; M. V. Krishnaraj (Natural Product Research, 2026)

Dietary Crataegus sinaica leaves enhance growth performance, antioxidant status, intestinal integrity, and regulate inflammation-related genes in Nile tilapia under melamine exposure - Walaa El-Houseiny; Abdallah Tageldein Mansour; Amany Behairy; Ahmed Saud Alsaqufi; Yousef Ahmed Alkhamis; Yasmina M. Abd-Elhakim; Mohamed Ashour; Roshmon Thomas Mathew; Ahmed O. Abbas; Bayan A. Hassan; Engy M. M. Mohamed; Yasmina K. Mahmoud (Frontiers in Marine Science, 2026)
Introduction Dietary exposure to melamine (MELA) adversely affects growth performance and intestinal health in Nile tilapia. This study evaluated the protective effects of Crataegus sinaica leaf extract (CSL) against MELA-induced toxicity. Methods In this study, a total of 240 fish (26.39 ± 0.22) were randomly assigned to four groups (60 fish/group; four replicates of 15 fish each). The control group received a basal diet, the CSL group received 1% CSL, the MELA group received 10 g/kg MELA, and the CSL+MELA group received both CSL (1%) and MELA (10 g/kg) for 60 days. Results MELA exposure significantly reduced growth performance, including final body weight (−26.78%), weight gain (−50.59%), specific growth rate (−41.41%), and feed intake (−20.50%) compared to the control, and increased feed conversion ratio (FCR). Conversely, CSL supplementation enhanced growth parameters, with increases in weight gain (33.88%), specific growth rate (21.88%), and FCR reduced by (20.57%). Co-administration of CSL with MELA partially restored growth, with final body weight, weight gain, and FCR approaching control values. MELA also suppressed digestive enzyme activities (lipase −21.38%, α-amylase −34.72%, protease −32.42%) and impaired intestinal antioxidant defenses (SOD −43.73%, CAT −37.88%, GPx −38.01%, GST −50%; MDA increased by 128.58%). CSL supplementation increased antioxidant enzyme activities (SOD + 17.20%, CAT + 57.58%, GPx +13.43%, GST + 28.95%) and restored digestive enzyme activity (lipase: +10.11%, α- amylase: +11.50%, and protease: +8.82%). At the molecular level, MELA significantly upregulated inflammatory genes ( tnf-α : 5.22 ± 0.35, tlr-4 : 3.01 ± 0.34, il-6 : 2.66 ± 0.11, il-8 : 2.65 ± 0.15) while CSL co-administration downregulated these genes and normalized il-10 expression (2.67 ± 0.15). Histopathological analysis confirmed that CSL mitigated MELA-induced intestinal damage, including epithelial denudation, inflammatory infiltration, hemorrhage, and goblet cell hyperplasia. Conclusion These findings showed that dietary CSL markedly promotes growth, enhances antioxidant defenses, modulates inflammatory responses, and protects intestinal integrity, demonstrating its potential as a natural dietary strategy to counteract MELA toxicity in Oreochromis niloticus .

High-resolution carbon isotope record from Svalbard reveals elevated atmospheric CO2 during the Middle Devonian Taghanic crisis - Annique van der Boon; Brian A. Schubert; William M. Hagopian; Mathew Domeier; A. Hope Jahren (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Heterogeneous iron-doped covalent triazine framework for the efficient photocatalytic upcycling of polystyrene waste to valuable aromatics under ambient conditions - Zeinab M. Saeed; Thaksen Jadhav; Renny Mathew; Xuan Li; Shamraiz H. Talib; Sasi Stephen; Andreas Kafizas; Franziska Emmerling; Dalaver H. Anjum; Ana Guilherme Buzanich; Brijith Thomas; Sharmarke Mohamed (Chemical Engineering Journal, 2026)

Functional roles of ginger (Zingiber officinale) in strengthening the physiological responses, growth, antioxidant/immune gene expression, and resistance to Fusarium oxysporum in Red Tilapia (Oreochromis sp.): in vivo and in silico approaches - Roshmon Thomas Mathew; Mohamed Ashour; Michelyne Haroun; Yousef Ahmed Alkhamis; Abdallah Tageldein Mansour; Ahmed Saud Alsaqufi; Hesham Abdallah Hassanien; Huda Ahmad Alamer; Hailah M. Almohaimeed; Ehab Faiyz Wahbah; Nashmiah S. Alshammari; Amal Ali Alharbi; et al. (Tropical Animal Health and Production, 2026)

Modulation of growth, blood physiology, disease resistance, molecular immune-antioxidant gene expression, and tissue integrity in european seabass (Dicentrarchus labrax) fed Moringa oleifera flower-enriched diets - Roshmon Thomas Mathew; Mohamed Ashour; Ehab El-Haroun; Abdallah Tageldein Mansour; Ahmed Saud Alsaqufi; Yousef Ahmed Alkhamis; Hailah M. Almohaimeed; Nehal A. Younis; Moaheda E.H. Eissa; El‐Sayed Hemdan Eissa (Frontiers in Marine Science, 2026)
Herbal-based additives are now recognized as effective tools of growth and immunity in aquaculture. Seeking these botanical alternatives is a practical necessity for sustainable farming and chemical reduction. Moringa oleifera flowers (MOF), in particular, offer significant potential due to their established history in treating inflammation and respiratory conditions. However, the potential of these additives to enhance growth, physiological status, and tissue health in European seabass ( Dicentrarchus labrax ) has not yet been evaluated. A 70-day feeding trial was conducted to evaluate the effects of graded dietary levels of M. oleifera flower (MOF) on the growth performance, immune- and antioxidant-related genes, physio-metabolic profile, and redox homeostasis of European seabass and resistance to Vibrio alginolyticus challenge. Fish were allocated to four experimental groups and fed either a basal diet (control, MOF0) or the basal diet supplemented with MOF at concentrations of 1 (MOF1), 2 (MOF2), and 3 (MOF3) g/kg. Dietary MOF supplementation significantly enhanced growth indices and the whole-body proximate composition of D. labrax compared to the control group (P< 0.05). Furthermore, fish fed MOF-enriched diets exhibited significant elevations in hematological parameters, including (hemoglobin, RBCs, MCH, MCHC, and WBC) counts (P< 0.05). Metabolic and antioxidant profiles were similarly improved, characterized by a significant increase in total serum protein and a concomitant reduction in glucose, cholesterol, and hepatic enzyme activities (AST, ALT, and ALP) (P< 0.05). Dietary MOF inclusion mitigated oxidative damage by decreasing MDA levels while simultaneously enhancing the enzymatic antioxidant defense system (SOD, CAT, and GPx) (P< 0.05). These biochemical improvements were supported by molecular data showing a significant upregulation of growth genes ( IGF-I and GH ), pro-inflammatory and complement system genes (IL-1β and C3 ), and antioxidant enzymes ( SOD and GPx ) (P< 0.05). MOF inclusion in the diets of D. labrax supported systemic tissue health by improving the structural integrity of the intestinal mucosa and preventing degenerative changes in the hepatic parenchyma and muscle fibers. These findings underscore the multi-tissue cytoprotective efficacy of MOF in D. labrax . Following the V. alginolyticus challenge, fish in the MOF2 and MOF3 groups exhibited significantly higher survival rates and enhanced pathogen resistance compared to the MOF0 and MOF1 cohorts (P< 0.05). Consequently, our data suggest that a dietary inclusion of 2 g/kg of M. oleifera flowers represents an effective strategy for optimizing growth performance, immunocompetence, and antioxidant capacity in European seabass.

Trends in extreme climate indices of the Amaravathi Basin, India: a spatiotemporal analysis - M Jothi Jeya Sri; Nisha Radhakrishnan; Aneesh Mathew; Surendar Natarajan (Journal of Earth System Science, 2026)

Comparative efficacy of silver nanoparticles from agro-industrial waste of cumin, anise, and banana peel against Fusarium oxysporum on common bean (Phaseolus vulgaris) - Reham Oraby; Amera N. Alqahtani; Laila A. AL-Essa; Hanan AlOmari; Merfat O. Aljhdli; Mari Sumayli; Ramadan Taha; Ahmed M. Saad; Lamia Elmaghraby; Taha F. Taha; Mohamed A. Taha; Walid F. A. Mosa; et al. (European Journal of Plant Pathology, 2026)
Fusarium oxysporum , the causal agent of root rot and vascular wilt in common bean ( Phaseolus vulgaris ), represents a substantial risk to legume cultivation. The current study offers a comparative examination of the antifungal efficacy of agro-industrial wastes from cumin ( Cuminum cyminum ), anise ( Pimpinella anisum ), and banana peel ( Musa paradisiaca ), and their green-synthesized silver nanoparticles (AgNPs), against F. oxysporum infecting P. vulgaris . The biosynthesized AgNPs were found to be spherical with tiny sizes ranging from 20, 25, and 35 nm for cumin-AgNPs, anise-AgNPs, and banana peel-AgNPs, respectively. The agro-industrial waste extracts revealed a diverse range of bioactive compounds that served as reducing agents. In vitro antifungal activity revealed a dose-dependent suppression of F. oxysporum mycelial proliferation. The half-maximal effective concentrations (EC 50 ) for the crude extracts ranged from 125 to 200 µg/mL. AgNPs showed markedly improved EC 50 values, ranging from 62.5 µg/mL in cumin-AgNPs to 100 µg/mL in banana-AgNPs. In vivo greenhouse experiments on infected P. vulgaris demonstrated that all treatments significantly decreased disease severity. Soil drench application of agro-industrial waste extracts reduced disease severity to 59.64% (cumin waste), 66.52% (anise waste), and 74.86% (banana peel), compared with 85.14% in the infected control. The AgNPs fabricated from agro-industrial wastes offered enhanced protection, decreased disease severity to 36.17% (cumin-AgNPs), 43.30% (anise-AgNPs), and 51.52% (banana peel-AgNPs). The applications significantly alleviated the physiological and oxidative stress caused by F. oxysporum . The cumin-AgNPs treatment significantly restored chlorophyll a and chlorophyll b content to 2.45 and 0.92 mg/g, respectively, comparable to the healthy control (2.50 and 0.95 mg/g) and much higher than the infected control (1.10 and 0.40 mg/g). Moreover, it triggered a defense response, markedly enhancing the activities of antioxidant enzymes, including peroxidase and polyphenol oxidase, in the treated plant compared with the infected control. The current findings clearly indicate that AgNPs synthesized from agro-industrial wastes could serve as effective, sustainable nanobiopesticides, surpassing the use of a single agro-industrial waste for the integrated management of Fusarium root rot and vascular wilt in common beans.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Enhanced modeling of directional data using truncated wrapped Akash distribution for geological and environmental applications - K. M. Sakthivel; Alicia Mathew (Modeling Earth Systems and Environment, 2026)

Microbial enzymes for plastic degradation: a comprehensive review of current status and emerging trends - M. Chekkath Shehbas; Dhanraj Sanjivkumar Desai; Tess Maria Mathew; K. Madhavan Nampoothiri (Biodegradation, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Guava leaf (Psidium guajava) byproducts in animal and fish diets: a review of health benefits, immunomodulation, and sustainable applications - Khaled M. Al-Marakby; Islam G. Abdelghani; Ehab El-Haroun; Zeinab Mahasneh; Roshmon Thomas Mathew; Asmaa M. Sheiha; Mohamed F. Abo El-Maati; El-Sayed Hemdan Eissa; Md Altafur Rahman; Sameh A. Abdelnour (Tropical Animal Health and Production, 2026)

Assessment of space weather modeling capabilities and transition to operations - Maria M. Kuznetsova; Martin A. Reiss; Edmund Henley; Eric Adamson; Suzy Bingham; Mario M. Bisi; François-Xavier Bocquet; Laura Boucheron; Min-Yang Chou; Claudio Corti; Gian Luca Delzanno; Richard A. Fallows; et al. (Advances in Space Research, 2026)

Morphological and Physiological Responses of Two Tropical Rice (Oryza sativa) Varieties to High-Temperature Stress - V. S. Anup; Pallot Sindhumole; Jiji Joseph; Deepu Mathew; M. S. Parvathi; B. R. Vishnu (Agricultural Research, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Thermal Conversion of Sugarcane Bagasse to Biochar and Its Application in Treatment of Methylene Blue Contaminated Water - T. Geetha; John K Smitha; Litty Mathew Irimpan; Manju Sebastian; V. Geetha; C. J. Theresa; Bincy Joseph; M. Nancy; K. Nimmy (Sugar Tech, 2026)

Structural, Electronic, and Molecular Dynamics Perspectives of Andrographolides as Potential CDK2 Inhibitors - Jisna Jose; Glowi Alasiri; Jibin K. Varughese; Ali M. Alaseem; Mohammad Fareed; Mohammad Suhail Akhter; Thomas V. Mathew (Journal of Pharmaceutical Innovation, 2026)

New insights into the potential effects of date palm seed powder supplementation on the growth, hemato-biochemical indices, organ histology, and gene expression in Rahmani sheep - Hesham S. Ghazzawy; Nashi K. Alqahtani; Roshmon Thomas Mathew; Hassan M. Ali-Dinar; Osama H. Mahmoud Hassan; Hebatallah M. Saad; Yasmin M. Abd El-Aziz; Ehab El-Haroun; Moaheda E.H. Eissa; El-Sayed Hemdan Eissa (Tropical Animal Health and Production, 2026)

The influence of postfire root strength decay on shallow landslide susceptibility in western Oregon - David F. M. Sousa; Erik Fulmer; Maryn A. Sanders; Nicolas W. Mathews; Joshua J. Roering; Francis K. Rengers; Benjamin B. Mirus; William J. Burns; Michael J. Olsen; Ben A. Leshchinsky (Landslides, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Unveiling the pharmacological potential of Ophiorrhiza radicans Gardner ex Thwaites: first report on its antioxidant, anti-inflammatory, antidiabetic, and cytotoxic activities - Jinu Mathew; Majid Sharifi-Rad; Krishnaraj M V; Mity Thambi (Natural Product Research, 2025)

Transcranial alternating current stimulation improves ballistic motor performance in trained and untrained limbs of healthy older adults - Nishadi N. Gamage; Wei-Yeh Liao; Philip J. Atherton; Mathew Piasecki; George M. Opie; John G. Semmler (GeroScience, 2025)

Perspectives on beach seine fishing in the Western Indian Ocean: A review - Gladys M. Okemwa; George W. Maina; Edward N. Kimani; Almubarak Abubakar; Mathew O. Silas; Catherine Mwakosya; Bernadine Everett; Rui J. Mutombene; Janet Mwangata; Hassan Yussuf; Willys Osore (Marine Policy, 2025)

Efficient synthetic natural gas production from direct air capture using titania-based dual function materials - Mathew J. Rasmussen; Sawyer Halingstad; Nathan C. Ellebracht; Melinda L. Jue; Alex Hill; Matthew M. Yung; Simon H. Pang (Chemical Engineering Journal, 2025)

Antimicrobial secondary metabolites from the leaves of Rhabdophyllum calophyllum (Hook.f.) Tiegh (Ochnaceae) and their chemophenetic significance - Baleba Mbanga Moise Roger; Denis-Gregoire Téné; Angélique Nicolas Messi; Patrice Bonny; Mathew M. Nindi; Bernard Bodo; Bintou Abderamane; Anastasie Ewola Tih; Raphael Tih Ghogomu (Biochemical Systematics and Ecology, 2025)

Bioactive Metabolites and ISSR Marker Assisted Selection Demonstrate the Diversity in Clitoria ternatea L. (Leguminosae) Morphotypes - Arya M. R; S. Suhara Beevy; Mathew Dan (Tropical Plant Biology, 2025)

Untangling tightly bound knots: a reappraisal of Campbellia (Orobanchaceae), with the rediscovery of C. aurantiaca after more than 175 years - P. M. Salim; Jose Mathew; P. T. Arunraj; V. N. Sanjai; B. Gopallawa (Kew Bulletin, 2025)

Wrapped Garima Distribution: A Circular Modeling Approach for Ecological and Environmental Data - K. M. Sakthivel; Alicia Mathew (Environmental Modeling & Assessment, 2025)

Dietary co-supplementation of Pediococcus acidilactici and bergamot essential oil improves growth, immune response, and disease resistance in sea bream (Sparus aurata) - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Ahmed Saud Alsaqufi; Abdallah Tageldein Mansour; Hesham Abdallah Hassanien; Abdullah Sheikh; Huda Ahmad Alamer; Hailah M. Almohaimeed; Ehab El-Haroun; El-Sayed Hemdan Eissa; Sameh A. Abdelnour (Aquaculture International, 2025)

Effects of quadric probiotic blend supplementation on growth, biochemical markers, organ histology, immunity, antioxidant status, and gene expression in Nile tilapia (Oreochromis niloticus) - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Ahmed Saud Alsaqufi; Abdallah Tageldein Mansour; Ouda Nasser Aldakhillalla; Mohamed Shawky El Sayed; Layla A. Almutairi; Zulhisyam Abdul Kari; Abdelazeem M. Algammal; Helal F. Hetta; Moaheda E. H. Eissa; El-Sayed Hemdan Eissa (Aquaculture International, 2025)

Evaluation of Groundnut (Arachis hypogaea) Genetic Variability for High-Temperature Tolerance in Controlled and Field Conditions - Anurag Mathew; Padma Vemulapalli; Lal Ahamed Mohammad; Rachana Bagudam; Sai Rekha Kadirimangalam; Anilkumar Vemula; M. Raghavendra; Janila Pasupuleti (Agricultural Research, 2025)

Potential symbiotic effects of date palm seed extract on growth, immunity, antioxidant activities, gut microbiota, expression levels, and Vibrio parahaemolyticus resistance in Shrimp - Roshmon Thomas Mathew; Nashi K. Alqahtani; Hesham S. Ghazzawy; Ehab El-Haroun; Yousef Ahmed Alkhamis; Abdallah Tageldein Mansour; Nagarajan Ganesan; Amel M. El Asely; Layla A. Almutairi; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; El-Sayed Hemdan Eissa (Frontiers in Marine Science, 2025)
Date Palm Seed Extract (DPSE) is known to possess beneficial health-promoting and growth-boosting properties, but its specific influence on whiteleg shrimp ( Litopenaeus vannamei) health and physiology has yet to be fully explored. Hence, this study examined how dietary DPSE inclusion impacted growth performance, antioxidant status, immune response, hepatic tissue health, inflammation-related gene expression, and resistance to Vibrio parahaemolyticus in shrimp. The study involved four experimental groups of shrimps that were fed diets with varying DPSE inclusions: 0 (DPSE0), 1 (DPSE1), 2 (DPSE2), and 4 (DPSE4) g/kg diet over a 70-day period. The results indicated that dietary DPSE supplementation led to significantly higher (P<0.05) concentrations of whole-body composition (crude protein, gross energy, and crude lipid) in the treated groups. Conversely, the ash content was significantly reduced (P<0.05) in all DPSE-treated shrimp groups compared to the shrimp fed the control diet. Shrimp-fed DPSE-supplemented diets showed a significantly higher total hemocyte count (THC) compared to the control group (P<0.05). The levels of immunological parameters (phagocytosis, phenoloxidase, and lysozyme) and antioxidant status (superoxide dismutase and catalase) were significantly improved with increasing dietary DPSE levels, indicating a dose-dependent effect (P<0.01). The supplementation of DPSE at 1, 2, and 4 g in shrimp diets significantly improved the mRNA expression of immune-related genes ( LGBP, PX, PPA ) and antioxidant genes ( cytMnSOD , mtMnSOD ) compared to the control group (P<0.001). Both total aerobic bacteria and total enteric bacteria were significantly reduced in all DPSE-supplemented groups (P<0.05) compared to the control diet. Dietary inclusion of DPSE improved hepatopancreas tissues and significantly increased resistance to Vibrio parahaemolyticus in shrimp. The results indicate that the dietary inclusion of DPSE can enhance the growth, disease resistance, and overall health of shrimp by regulating immune function, antioxidant status, and immune associated genes regulation. This highlights its potential for sustainable and environmentally beneficial applications in aquaculture.

Impact of an Adapted Group Lifestyle Balance Program on Weight Loss and Physical Activity Uptake Among Adolescent Bariatric Surgery Patients - M. Misserian; F. Jackson; A. Wheelington; R. King; M. Mathew; M. Allicock; B. Cartwright; A. Chandrasekhar; D. Polavarapu; F. Qureshi; S. Barlow; S. Messiah (Journal of the Academy of Nutrition and Dietetics, 2025)

Association Between Household Food Security, Dietary Quality and Breastfeeding Duration: An Analysis of NHANES 2015-2018 - S. Samuel; R. Mathews; J. Komakech; M. Yang (Journal of the Academy of Nutrition and Dietetics, 2025)

The odds and costs of ambulance attendances associated with heatwave severity in older adults of queensland, Australia - Zhiwei Xu; Shannon Rutherford; Son Nghiem; Hannah M. Mason; Blesson Mathew Varghese; Jemma C. King; Amy E. Peden; Kerrianne Watt; Emma Bosley; Richard C. Franklin (International Journal of Biometeorology, 2025)
Ambulance attendances have been increasingly reported to be a sensitive indicator of increased health service utilisations during heatwaves. This study estimated the odds and costs of ambulance attendances associated with heatwave severity (low-intensity, severe, and extreme) in older adults (≥ 65 years) from 1st January 2010 to 31st December 2018 in the State of Queensland, Australia. The findings showed that low-intensity, severe, and extreme heatwaves were associated with 1.4% (95% confidence interval: 0.3%, 2.5%), 4.1% (2.1%, 6.1%), and 9.7% (7.3%, 12.0%) increased odds of ambulance attendances for older adults, respectively. The increased odds of ambulance attendances elevated with age during extreme heatwaves (peaking at 11.7% for ≥ 85 years). Heatwaves were associated with additional ambulance attendance costs of $237,141 per year for older adults in Queensland, with 62.2% and 31.7% of these costs from low-intensity and severe heatwaves, respectively. These findings call for research to address critical knowledge gaps around appropriate early warning system notifications for low-intensity and severe heatwaves, given their evidenced impacts on individuals and emergency health systems.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Effects of polystyrene nanoplastics on the female reproductive system in mice: Implications for ovarian function and follicular development - Mahsa Gholiof; Jocelyn M. Wessels; Warren G. Foster; Victoria Turpin; Mathew Leonardi (Reproductive Toxicology, 2025)

Synergistic Use of Scatterometer and Ocean Colour Monitor Onboard EOS-06 Satellite for Various Oceanographic Applications - Neeraj Agarwal; Jishad M; Jai Kumar; Sanjiba Kumar Baliarsingh; Naga Swetha; Smitha Ratheesh; Suchandra Aich Bhowmick; Ratheesh Ramakrishnan; Abhisek Chakraborty; Rajesh Shikakoli; Manche Shiva Shankar; Reema Mathew; et al. (Journal of the Indian Society of Remote Sensing, 2025)

Coexistence beyond disciplinary silos: Five dimensions of analysis for more convivial human-predator interactions - Judith E. Krauss; Valentina Fiasco; Silvio Marchini; Alex McInturff; Laila T. Sandroni; Peter S. Alagona; Dan Brockington; Bram Büscher; Rosaleen Duffy; Katia Maria P M de Barros Ferraz; Rob Fletcher; Wilhelm Andrew Kiwango; et al. (Biological Conservation, 2025)

Combining Observations and Models: A Review of the CARDAMOM Framework for Data‐Constrained Terrestrial Ecosystem Modeling - Matthew A. Worden; T. Eren Bilir; A. Anthony Bloom; Jianing Fang; Lily P. Klinek; Alexandra G. Konings; Paul A. Levine; David T. Milodowski; Gregory R. Quetin; T. Luke Smallman; Yinon M. Bar‐On; Renato K. Braghiere; et al. (Global Change Biology, 2025)
The rapid increase in the volume and variety of terrestrial biosphere observations (i.e., remote sensing data and in situ measurements) offers a unique opportunity to derive ecological insights, refine process‐based models, and improve forecasting for decision support. However, despite their potential, ecological observations have primarily been used to benchmark process‐based models, as many past and current models lack the capability to directly integrate observations and their associated uncertainties for parameterization. In contrast, data assimilation frameworks such as the CARbon DAta MOdel fraMework (CARDAMOM) and its suite of process‐based models, known as the Data Assimilation Linked Ecosystem Carbon Model (DALEC), are specifically designed for model‐data fusion. This review, motivated by a recent CARDAMOM community workshop, examines the development and applications of CARDAMOM, with an emphasis on its role in advancing ecosystem process understanding. CARDAMOM employs a Bayesian approach, using a Markov Chain Monte Carlo algorithm to enable data‐driven calibration of DALEC parameters and initial states (i.e., carbon pool sizes) through observation operators. CARDAMOM's unique ability to retrieve localized model process parameters from diverse datasets—ranging from in situ measurements to global satellite observations—makes it a highly flexible tool for analyzing spatially variable ecosystem responses to environmental change. However, assimilating these data also presents challenges, including data quality issues that propagate into model skill, as well as trade‐offs between model complexity, parameter equifinality, and predictive performance. We discuss potential solutions to these challenges, such as reducing parameter equifinality by incorporating new observations. This review also offers community recommendations for incorporating emerging datasets, integrating machine learning techniques, strengthening collaboration with remote sensing, field, and modeling communities, and expanding CARDAMOM's relevance for localized ecosystem monitoring and decision‐making. CARDAMOM enables a deep, mechanistic understanding of terrestrial ecosystem dynamics that cannot be achieved through empirical analyses of observational datasets or weakly constrained models alone.

Satellite tracking reveals sex-specific differences in the geographical and vertical habitat use of Whale sharks, Rhincodon typus, in the Eastern Indian ocean - Colby J. Bignell; Toby A. Patterson; Anthea Donovan; Mathew A. Vanderklift; Wayne Rochester; Jayson M. Semmens; Richard D. Pillans (Marine Biology, 2025)
Satellite tagging of whale sharks ( Rhincodon typus) has typically focused on juvenile males which dominate coastal aggregation sites, with limited data on the movements of females. We satellite-tagged 39 whale sharks of 3.75–9.27 m total length at Ningaloo reef between 2015 and 2018 with a roughly equivalent sex ratio (Male = 20, Female = 18, Unknown = 1).We aimed to identify differences in horizontal and vertical movements between the sexes using state-space models, kernel utilisation distributions (KUDs) and generalised additive models (GAMs). Deployment spans ranged from 9 to 340 days (mean = 132.4 ± SE = 17.9 days, N = 35) and 22 tracks exceeded 1000 km in length (mean = 2557 ± SE = 370 km, N = 35). Whale sharks spent > 90% of time in epipelagic waters ≤ 200 m and dived to a maximum depth of 1906 m. Sex-specific differences in horizontal and vertical movements were related to distinct temperature preferences. Females spent more time in offshore waters and preferred cooler Sea Surface Temperatures (SST) than males. Female movements were strongly influenced by increasing SSTs with greater space and depth use, while the space and depth use of males was more consistent with SSTs < 28 °C. We found no relationships between whale shark size and their space, depth or temperature use, though most individuals were immature (< 8 m, N = 24). The results provide novel evidence of sex-specific horizontal and vertical movements over broad geographical scales, extending current knowledge on the movement ecology and sex-specific demography of this endangered species.

Impact of arm movement strategies on emotional state and gait outcomes during height-induced postural threat in healthy children compared to young adults - Anna M. Wissmann; Mathew W. Hill; Thomas Muehlbauer; Johanna Lambrich (Experimental Brain Research, 2025)
Empirical evidence indicates that height-induced postural threat as well as the restriction of arm movements lead to detrimental effects on walking performance. However, it is unclear whether the deteriorations are more pronounced in children (i.e., due to incomplete maturation) compared to young adults. This study investigated the effects of different arm movement strategies on subjective and objective indicators related to walking at or above ground-level in children compared to young adults. Twenty-nine children (age: 11.1 ± 0.3 years) and 26 young adults (age: 24.0 ± 4.7 years) walked five meters at self-selected speed on ground-level (no threat) and 80 cm above ground-level (threat) with free and restricted arm movements. Walking outcomes (i.e., gait speed, cadence) were measured and used as objective markers. Self-reported emotional state outcomes (i.e., balance confidence, fear of falling, perceived safety, conscious balance processing) were assessed and used as subjective indicators related to walking. Children significantly differed from young adults in objective and subjective outcomes related to gait by showing no decrease in walking cadence from the no threat to the threat condition (irrespective of arm movement condition) and a decrease in perceived safety when walking with restricted compared to free arm movements (irrespective of threat condition). The findings extend previous research related to postural threat and arm restriction while walking in young adults and provide new insights into understanding how children behave under these conditions.

Operational insights and measurements of ChaSTE on the Chandrayaan 3 Vikram Lander - Nizy Mathew; M. Ram Prabhu; V. Aasik; Fazil Mohammad; Dinakar Prasad Vajja; P.P. Pramod; Kiran John Antony; M. Satheesh Chandran; K.P. Subhajayan; V. Sathiyamoorthy (Advances in Space Research, 2025)

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

Mangrove Community Structure Following Dieback Events in the Maldives: Special Emphasis on the Genus Bruguiera - S. Sreelekshmi; Deepak Jose; B. Aneesh; Aishath Farhath Ali; S. Bijoy Nandan; K. Avarachen Mathew; M. Harikrishnan; P. Hari Praved (Thalassas: An International Journal of Marine Sciences, 2025)

Morphological and Genetic Diversity of Indian Clitoria ternatea L. (Faboideae, Fabaceae) Morphotypes Inferred from Floral Characters and SCoT Markers - Arya M. R.; S. Suhara Beevy; Mathew Dan (Plant Molecular Biology Reporter, 2025)

Inhibition of monoamine oxidases and neuroprotective effects: chalcones vs. chromones - Reshma Ipe; Jong Min Oh; Sunil Kumar; Iqrar Ahmad; Lekshmi R. Nath; Sandeep Bindra; Harun Patel; Krishna Yallappa Kolachi; Prabitha Prabhakaran; Prashant Gahtori; Asad Syed; Abdallah M. Elgorbanh; et al. (Molecular Diversity, 2025)

The combination of composted animal manure and plant growth-promoting rhizobacteria is a sustainable biofertilizer and bionematicide for grapevine (Vitis vinifera L.) cultivars - Osama M. M. Khder; Ramadan M. El-Ashry; Ahmed M. A. El-Deeb; Nahla A. Bouqellah; Mada F. Ashkan; Anas S. Dablool; Felwa A. Thagfan; Uthman B. Algopishi; Naheda M. Alshammari; Hawazen K. Al‑Gheffari; Ahmed M. Fikry; Mohamed T. El-Saadony; et al. (European Journal of Plant Pathology, 2025)
Root-knot nematodes (RKN) cause extensive damage to grapevine cultivars. RKN-resistant grapevine rootstocks remain vulnerable to biotic and abiotic stresses. This study aimed to determine the influence of composted animal manures (CAMs) [chicken manure (CM), cow manure (CowM), and sheep manure (SM)] with or without plant growth-promoting rhizobacteria (PGPR) on the population of Meloidogyne incognita , free-living nematodes (FLNs) and predaceous nematodes (PNs) residing in the soils of vineyard cultivars (Flame, Superior and Prime). The nematodes were isolated from grapevine roots and rhizosphere soils, then the absolute frequency of occurrence (FO), relative FO, prominence value (PV), and population density (PD) were assessed. The impact of CAMs and PGPR on the growth parameters, fruit output, and quality of three grapevine varieties was subsequently evaluated. Eight treatments included a control without CAMs or PGPR amendments, the CAMs alone, or CAM treatments combined with PGPR. The results showed that FLNs and PNs were more abundant in Prime than Flame or Superior cultivars when poor sandy loam soils were supplied with CAMs. Among all tested manures, CM was the best treatment as a nematicide. This was evident from the decreased numbers of M. incognita and increased numbers of FLNs and PNs in grapevine fields. Compared to the soil-applied oxamyl (a systemic nematicide), which was efficiently suppressive on M. incognita for two months, CM significantly ( P < 0.05) decreased PD of the phytonematodes for five months, improved soil structure and enhanced the soil biological activities. There were significant ( P < 0.05) increases in the number of leaves/vines by 79.9, 78.8, and 73.1%; and total fruit weight/vine by 76.9, 75.0, and 73.0% in Flame, Superior, and Prime varieties, respectively, compared to untreated vines. Regardless of the cultivar, soils amended with CM + PGPR achieved the lowest number of M. incognita among all other treatments, followed by SM + PGPR and CowM + PGPR. It was concluded that CAMs amendment, mainly CM, along with PGPR in poor sandy soils of temperate areas, is considered a sustainable approach for reducing parasitic nematodes and improving agricultural management.

Addressing global food security in Africa through training of next generation of researchers in plant pest diagnostics, in vitro culture, and clean plant production - Sadanand A. Dhekney; Simon Zebelo; Papaiah Sardaru; Purushothaman Natarajan; Stephan L. Tubene; Caleb Nindo; Lyna F. T. Mukwa; Mathews M. Dida; Moses T. Kairo (In Vitro Cellular & Developmental Biology - Plant, 2025)

The role of histological stains in aquaculture and fisheries development technology - El-Sayed Hemdan Eissa; Alkhateib Y. Gaafar; Roshmon Thomas Mathew; Eman A. Al-Shahari; Ekemini Moses Okon; Moaheda E. H. Eissa; Yasmin M. Abd El-Aziz (Aquaculture International, 2025)

Bilateral neuromuscular adaptation to acute unilateral resistance exercise in healthy older adults - Nishadi N. Gamage; Abdulmajeed Altheyab; Yuxiao Guo; Bethan E. Phillips; George M. Opie; John G. Semmler; Philip Atherton; Mathew Piasecki (GeroScience, 2025)
Resistance exercise (RE) enhances functionality in older adults and has proven effective as a means of cross-education in scenarios of unilateral disuse. However, the extent to which older adults demonstrate cross-limb transfer at the motor unit (MU) level following a single bout of unilateral RE is unclear. Thirteen healthy older adults (74.9 ± 4.8 years; 5 females) underwent bilateral neuromuscular assessments pre- and post- a single bout of unilateral RE consisting of sets of 12 repetitions of leg extension of the dominant (exercise) leg, at 75% of 1 repetition maximum, performed to failure. Maximum voluntary contraction (MVC) and force steadiness (FS) were measured. Central and peripheral features of individual MU were recorded using high-density surface electromyography and intramuscular electromyography (HDs/iEMG), during contractions normalised to 25% MVC. Following unilateral RE, MVC reduced in exercise (-14.8%, p < 0.001) and control (-6.9%, p = 0.003) legs, with reduced FS performance in the exercise leg compared to the control (p = 0.002). MU firing rate increased during contractions normalised to 25% baseline MVC in the exercised leg ( p < 0.05), with no adaptation in the control leg ( p > 0.05). All iEMG recorded measures of MU potentials remained unchanged in both legs (all p > 0.05). Acute unilateral RE leads to bilateral MVC reduction in older males and females, demonstrating the cross-limb transfer effect. However, adaptation of MU features was only apparent in the exercised limb, and mechanisms underlying the force decline in the non-exercised limb remain uncertain.

Palaeoenvironmental reconstruction of a fjord catchment NW Scotland, UK since the Last Glacial Maximum: A multi-geochemical approach - Jennifer Taylor; David Selby; Jeremy M. Lloyd; Craig Smeaton; James Bendle; Mathew Allison; Yuan Ling; Luca Podrecca; Bradley B. Sageman; William Austin; Sönke Szidat (Quaternary Science Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Exploring machine learning models to predict atmospheric water harvesting with an ion deposition membrane - Giulio Barletta; Shashwata Moitra; Sybil Derrible; Alex Mathew; Anoop Muraleedharan Nair; Constantine M. Megaridis (Journal of Water Process Engineering, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Chandra’s surface thermophysical experiment (ChaSTE) onboard Chandrayaan 3 Lander - Nizy Mathew; K. Durga Prasad; Dinakar Prasad Vajja; V. Aasik; Fazil Mohammad; P.P. Pramod; M. Satheesh Chandran; Kiran John Antony; M. Ram Prabhu; M.B. Dhanya; Manu V. Unnithan; Shiju G. Thomas; et al. (Advances in Space Research, 2025)

Ecological connectivity and in-kind mitigation in a regulatory decision framework: A case study with an amphibian habitat specialist - Evin T. Carter; Bryce S. Wade; R. Trent Jett; Teresa J. Mathews; Lindsey E. Hayter; Sarah E. Darling; Jamie M. Herold; Greg Byrd; Christopher R. DeRolph; M. Kitty McCracken; Mark J. Peterson (Journal of Environmental Management, 2025)

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

Potential of dehydroepiandrosterone and quercetin to ameliorate copper oxide nanoparticles induced hepatotoxicity in albino wistar rats - Ahmed S. Ahmed; Liju S. Mathew; Asim S. Khan; Mark M. Rohn; Omaima K. Docmac; Pallav Sengupta; Ehab M. Hantash; Rasha A. Elsisy (Journal of Molecular Histology, 2025)

Techno-Economic Analysis of Biodiesel Production from Chlorella vulgaris Using Different Potential Biorefinery Approaches - Sudhanthiran M.C.; Muttu Pandian P.; Febin Mathew; M. Perumalsamy (BioEnergy Research, 2025)

4-octyl itaconate improves water quality, growth, immunity, blood parameters, and disease resistance of Nile tilapia (Oreochromis niloticus) infected with Aeromonas hydrophila - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Rashid Saleh Alngada; Raed Abdul Whed; Nouh Abdulaziz Aljaafari; El-Sayed Hemdan Eissa; Abdelazeem M. Algammal; Mohammad Bodrul Munir; Moaheda E. H. Eissa; Sameh A. Abdelnour (Aquaculture International, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Analysis of biokinetic parameters reveals patterns in mercury accumulation across aquatic species - Louise M. Stevenson; Paul G. Matson; Rachel M. Pilla; Simon Pouil; Tom J. Geeza; Amber Hills; Zapporah Ellis; Sydney Smith; Teresa J. Mathews (Science of The Total Environment, 2025)

Retraction notice to “A biorefinery-based approach for the production of ethanol from enzymatically hydrolysed cotton stalks” [Bioresource Technol. 242 (2017) 178–183] - Meera Christopher; Anil K. Mathew; M. Kiran Kumar; Ashok Pandey; Rajeev K. Sukumaran (Bioresource Technology, 2025)

Influence of mixed Rossby-Gravity waves on the North-East monsoon rainfall over south India - M. Kartheek; K. Nithya; Vincent Mathew; S. Sijikumar (Advances in Space Research, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Survey of prospective techniques for molten salt reactor feed monitoring - Steve E. Skutnik; Peter W. Sobel; Mathew W. Swinney; Karen K. Hogue; Maggie M. Arno; Sunil S. Chirayath (Annals of Nuclear Energy, 2024)

A new species of an endemic termite Ampoulitermes zacharia sp.nov (Blattodea: Isoptera: Termitidae: Nasutitermitinae) from Idukki, Kerala, India - Edwin Joseph; Sony Joseph; V. P. Sandra; M. D. Jerin; Anita Binu; B. Radhika; S. Samyuktha; Liz Merin Renjith; Jobin Mathew (International Journal of Tropical Insect Science, 2024)

Wastewater-based surveillance of SARS-CoV-2: Short-term projection (forecasting), smoothing and outlier identification using Bayesian smoothing - Douglas G. Manuel; Gauri Saran; Ivan Lee; Warsame Yusuf; Mathew Thomson; Élisabeth Mercier; Vince Pileggi; R. Michael McKay; Ryland Corchis-Scott; Qiudi Geng; Mark Servos; Heather Ikert; et al. (Science of The Total Environment, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Revitalizing dredged soils through chemical-physical combined method: A feasibility study - Kishore M S; Gayathri S; D. Akhil Varma; Jeevan Mathew Tharayil (Marine Georesources & Geotechnology, 2024)

Using Reported Intake and Skin Carotenoid Status to Understand Adolescents’ Perceptions About the Adequacy of Their Fruit and Vegetable Intake Characterized by the Stages of Change Transtheoretical Model - M. Badolato; K. Shelnutt; L. House; A. Mathews (Journal of the Academy of Nutrition and Dietetics, 2024)

Behavioral Frameworks and Translational Applications of Culinary Medicine and Culinary Nutrition - Andrea M. Krenek; Amy R. Mobley; Jeanette Andrade; Wendy Dahl; Anne E. Mathews (Journal of Nutrition Education and Behavior, 2024)

Unravelling the impact of lower vacuum activation temperature on Fe2+/Fe3+ mixed-valence unsaturated iron centres in MIL-101(Fe) and its impact on Fenton degradation of acetaminophen - Keerthi M. Nair; Nishanth Thomas; Sreedhanya Pallilavalappil; Snehamol Mathew; Karen Deignan; Steven J. Hinder; Barry Brennan; Fiona McArdle; Suresh C. Pillai (Journal of Environmental Chemical Engineering, 2024)

One-pot synthesis of stable vitamin C analogue using trans-glycosylating enzyme from Aspergillus carbonarius BTCF 5 - Reshma M. Mathew; Meena Sankar; Athiraraj Sreeja-Raju; Prajeesh Kooloth-Valappil; Anoop Puthiyamadam; Dileep Raveendran-Nair; Rajeev K. Sukumaran (Biocatalysis and Agricultural Biotechnology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Development, Pharmacokinetics and Antimalarial Evaluation of Dose Flexible 3D Printlets of Dapsone for Pediatric Patients - Adnan A. Khan; Tahir Khuroo; Eman M Mohamed; Sathish Dharani; Kayalar Canberk; Xiaoyu Zhang; Lamba Omar Sangaré; Mathew A. Kuttolamadom; Allison C. Rice-Ficht; Ziyaur Rahman (AAPS PharmSciTech, 2024)

Ecological impacts and management strategies of pesticide pollution on aquatic life and human beings - Synan F. AbuQamar; Mohamed T. El-Saadony; Samar S. Alkafaas; Mohamed I. Elsalahaty; Sara S. Elkafas; Betty T. Mathew; Amal N. Aljasmi; Hajar S. Alhammadi; Heba M. Salem; Taia A. Abd El-Mageed; Rashed A. Zaghloul; Walid F.A. Mosa; et al. (Marine Pollution Bulletin, 2024)

Incorporating Halal Into Healthy and Equitable Dietary Patterns to Address Food and Nutrition Security Among K-12 and University Students: A Perspective - Amelia Keleher; Meira Neggaz; Christine M. Cliff; YaQutullah Ibraheem Muhammad; Anne Mathews; Habeeb Quadri; Ridwan Abdul Rashid; Nadeem Zafar; Asma Ahad (Journal of Nutrition Education and Behavior, 2024)

Exercise protects the hypothalamus morphology from the deleterious effects of high sucrose diet consumption - Ahmed S. Ahmed; Liju S. Mathew; Marwa M. Mona; Omaima K. Docmac; Hoda A. Ibrahim; Amira M. Elshamy; Ehab M. Hantash; Rasha A. Elsisy (Journal of Molecular Histology, 2024)

Novel typing scheme reveals emergence and genetic diversity of Chlamydia pecorum at the local management scale across two koala populations - Cristina M. Fernandez; Mark B. Krockenberger; Simon Y.W. Ho; Mathew S. Crowther; Valentina S.A. Mella; Martina Jelocnik; Lachlan Wilmott; Damien P. Higgins (Veterinary Microbiology, 2024)

Novel in-genome based analysis demonstrates the evolution of OmpK37, antimicrobial resistance gene from a potentially pathogenic pandrug resistant Klebsiella pneumoniae MS1 isolated from healthy broiler feces - Sreejith Sreekumaran; Priya V K; Manjusha Premnath; Prathiush P R; Anisha M N; Jyothis Mathew; Jayachandran K; Radhakrishnan E K (Science of The Total Environment, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Correction to: Impact of heat stress on physio-biochemical parameters during early lactation of crossbred dairy cattle - Athulya Swaminathan; V. Beena; V. Babitha; V. S. Parvathy; M. Shynu; Joy Greeshma; V. L. Gleeja; P. S. Megha; Mathew J. Kulamkuthiyil; B. Ragupathi; V. Ramnath; Surej Joseph Bunglavan (Theoretical and Applied Climatology, 2024)

Impact of heat stress on physio-biochemical parameters during early lactation of crossbred dairy cattle - Athulya Swaminathan; V. Beena; V. Babitha; V. S. Parvathy; M. Shynu; Joy Greeshma; V. L. Gleeja; P. S. Megha; Mathew J. Kulamkuthiyil; B. Ragupathi; V. Ramnath; Surej Joseph Bunglavan (Theoretical and Applied Climatology, 2024)

A layered gabbro-anorthosite suite from Attappadi: Chemical and isotopic signature of Neoarchean subduction tectonics in the Southern Granulite Terrane, India - K.V. Kavyanjali; Y. Anilkumar; M. Santosh; Cheng-Xue Yang; K.S. Anoop; Anjana Mathew; Sanghoon Kwon (Lithos, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Therapeutic management of osteodystrophia fibrosa in early weaned Malabari male goat kids - Sabu Mathews Mevin; Y. Ajith; Sasi Adithya; Raj V. Amal; N. Athira; M. Sonaa; S. Raj Siji; Thankachan Ancy (Veterinary Research Communications, 2024)

Flooding, season and habitat interact to drive changes in vertebrate scavenging and carcass persistence rates - Zyna Krige; Emma E. Spencer; Mathew S. Crowther; Christopher R. Dickman; Thomas M. Newsome (Oecologia, 2024)
Scavenging dynamics are influenced by many abiotic and biotic factors, but there is little knowledge of how scavengers respond to extreme weather events. As carrion is a major driver of the organisation and structure of food webs within ecological communities, understanding the response of scavengers to extreme weather events is critical in a world that is increasingly subject to climate change. In this study, vertebrate scavenging and carcass persistence rates were quantified in the Simpson Desert of central Australia; a system that experiences major fluctuations and extremes in weather conditions. Specifically, a total of 80 adult red kangaroo ( Osphranter rufus ) carcasses were placed on the landscape and monitored using remote sensor cameras. This included 40 carcasses monitored before and then 40 carcasses monitored after a major flooding event. The carcasses were monitored equally before and after the flood across different seasons (warm and cool) and in dune and interdune habitats. Overall, a total of 8124 scavenging events for 97,976 visitation minutes were recorded for 11 vertebrate species within 30 days of carcass placement pre- and post-flood. Vertebrate scavenging increased post-flood in the warm season, especially by corvids which quadrupled their scavenging events during this time. There was little difference in carcass persistence between habitats, but carcasses persisted 5.3-fold longer post-flood in warm seasons despite increased vertebrate scavenging. The results demonstrate that a flood event can influence scavenging dynamics and suggest a need to further understand how seasons, habitats and extreme weather events can drive changes in carrion-based food webs.

Novel community data in ecology-properties and prospects - Florian Hartig; Nerea Abrego; Alex Bush; Jonathan M. Chase; Gurutzeta Guillera-Arroita; Mathew A. Leibold; Otso Ovaskainen; Loïc Pellissier; Maximilian Pichler; Giovanni Poggiato; Laura Pollock; Sara Si-Moussi; et al. (Trends in Ecology & Evolution, 2024)

The economics of nature's healing touch: A systematic review and conceptual framework of green space, pharmaceutical prescriptions, and healthcare expenditure associations - Muhammad Mainuddin Patwary; Mondira Bardhan; Matthew H.E.M. Browning; Thomas Astell-Burt; Matilda van den Bosch; Jiaying Dong; Angel M. Dzhambov; Payam Dadvand; Tracy Fasolino; Iana Markevych; Olivia McAnirlin; Mark J. Nieuwenhuijsen; et al. (Science of The Total Environment, 2024)

Biometeorological analysis on the molecular incidence of babesiosis and ehrlichiosis in dogs - Y. Ajith; Sasi Adithya; Varuna P. Panicker; N. Athira; V. Beena; M. Saifudeen Safeer; P. Preena; A. R. Nisha; C. Divya; S. G. Sangeetha; C. G. Umesh; R. C. Sundararajan; et al. (Theoretical and Applied Climatology, 2024)

A conditional mutation in a wheat (Triticum aestivum L.) gene regulating root morphology - Deying Zeng; Brett Ford; Jaroslav Doležel; Miroslava Karafiátová; Mathew J. Hayden; Tina M. Rathjen; Timothy S. George; Lawrie K. Brown; Peter R. Ryan; Filomena A. Pettolino; Ulrike Mathesius; Emmanuel Delhaize (Theoretical and Applied Genetics, 2024)
Key message Characterisation and genetic mapping of a key gene defining root morphology in bread wheat. Abstract Root morphology is central to plants for the efficient uptake up of soil water and mineral nutrients. Here we describe a conditional mutant of hexaploid wheat ( Triticum aestivum L.) that when grown in soil with high Ca 2+ develops a larger rhizosheath accompanied with shorter roots than the wild type. In wheat, rhizosheath size is a reliable surrogate for root hair length and this was verified in the mutant which possessed longer root hairs than the wild type when grown in high Ca 2+ soil. We named the mutant Stumpy and showed it to be due to a single semi-dominant mutation. The short root phenotype at high Ca 2+ was due to reduced cellular elongation which might also explain the long root hair phenotype. Analysis of root cell walls showed that the polysaccharide composition of Stumpy roots is remodelled when grown at non-permissive (high) Ca 2+ concentrations. The mutation mapped to chromosome 7B and sequencing of the 7B chromosomes in both wild type and Stumpy identified a candidate gene underlying the Stumpy mutation. As part of the process to determine whether the candidate gene was causative, we identified wheat lines in a Cadenza TILLING population with large rhizosheaths but accompanied with normal root length. This finding illustrates the potential of manipulating the gene to disconnect root length from root hair length as a means of developing wheat lines with improved efficiency of nutrient and water uptake. The Stumpy mutant will be valuable for understanding the mechanisms that regulate root morphology in wheat.

Correction: Comparative Study of Dermal Pharmacokinetics Between Topical Drugs Using Open Flow Microperfusion in a Pig Model - Manfred Bodenlenz; Thean Yeoh; Gabriel Berstein; Shibin Mathew; Jaymin Shah; Christopher Banfield; Brett Hollingshead; Stefanus J. Steyn; Sarah M. Osgood; Kevin Beaumont; Sonja Kainz; Christian Holeček; et al. (Pharmaceutical Research, 2024)

Comparative Study of Dermal Pharmacokinetics Between Topical Drugs Using Open Flow Microperfusion in a Pig Model - Manfred Bodenlenz; Thean Yeoh; Gabriel Berstein; Shibin Mathew; Jaymin Shah; Christopher Banfield; Brett Hollingshead; Stefanus J. Steyn; Sarah M. Osgood; Kevin Beaumont; Sonja Kainz; Christian Holeček; et al. (Pharmaceutical Research, 2024)
Purpose Accurate methods to determine dermal pharmacokinetics are important to increase the rate of clinical success in topical drug development. We investigated in an in vivo pig model whether the unbound drug concentration in the interstitial fluid as determined by dermal open flow microperfusion (dOFM) is a more reliable measure of dermal exposure compared to dermal biopsies for seven prescription or investigational drugs. In addition, we verified standard dOFM measurement using a recirculation approach and compared dosing frequencies (QD versus BID) and dose strengths (high versus low drug concentrations). Methods Domestic pigs were topically administered seven different drugs twice daily in two studies. On day 7, drug exposures in the dermis were assessed in two ways: (1) dOFM provided the total and unbound drug concentrations in dermal interstitial fluid, and (2) clean punch biopsies after heat separation provided the total concentrations in the upper and lower dermis. Results dOFM showed sufficient intra-study precision to distinguish interstitial fluid concentrations between different drugs, dose frequencies and dose strengths, and had good reproducibility between studies. Biopsy concentrations showed much higher and more variable values. Standard dOFM measurements were consistent with values obtained with the recirculation approach. Conclusions dOFM pig model is a robust and reproducible method to directly determine topical drug concentration in dermal interstitial fluid. Dermal biopsies were a less reliable measure of dermal exposure due to possible contributions from drug bound to tissue and drug associated with skin appendages.

In Vitro and In Vivo testing of 3D-Printed Amorphous Lopinavir Printlets by Selective Laser Sinitering: Improved Bioavailability of a Poorly Soluble Drug - Canberk Kayalar; Nada Helal; Eman M. Mohamed; Sathish Dharani; Tahir Khuroo; Mathew A. Kuttolamadom; Ziyaur Rahman; Mansoor A. Khan (AAPS PharmSciTech, 2024)

Assessment of Factors Affecting Sleep Quality in Geriatric Patients: A Cross-sectional Single Centre Study - Emy Susan Thomas; Greeshma Mathew; Prajnashree; Sophia M. George; U. P. Nandakumar; Chethan Subramanya (Sleep and Vigilance, 2024)

Remedial effectiveness of a pond biomanipulation: Habitat value and concentrations of polychlorinated biphenyls in fish - Rebecca A. Efroymson; Mark J. Peterson; R. Trent Jett; Natalie A. Griffiths; Evin T. Carter; Allison M. Fortner; Christopher R. DeRolph; Peijia Ku; Paul G. Matson; Rachel M. Pilla; Teresa J. Mathews (Journal of Hazardous Materials, 2024)

Response of organic aerosol to Delhi's pollution control measures over the period 2011–2018 - James M. Cash; Chiara Di Marco; Ben Langford; Mathew R. Heal; Tuhin K. Mandal; Sudhir K. Sharma; Bhola Ram Gurjar; Eiko Nemitz (Atmospheric Environment, 2023)

Normobaric hypoxia does not influence the sural nerve cutaneous reflex during standing - Mathew I. B. Debenham; Christina D. Bruce; Juliana M. Rancier; Chris J. McNeil; Brian H. Dalton (Experimental Brain Research, 2023)

Unifying the validation of ambient solar wind models - Martin A. Reiss; Karin Muglach; Richard Mullinix; Maria M. Kuznetsova; Chiu Wiegand; Manuela Temmer; Charles N. Arge; Sergio Dasso; Shing F. Fung; José Juan González-Avilés; Siegfried Gonzi; Lan Jian; et al. (Advances in Space Research, 2023)

Fluid migration pathways to groundwater in mature oil fields: Exploring the roles of water injection/production and oil-well integrity in California, USA - Peter B. McMahon; Mathew K. Landon; Michael J. Stephens; Kim A. Taylor; Janice M. Gillespie; Tracy A. Davis; David H. Shimabukuro (Science of The Total Environment, 2023)

Vascular senescence and leak are features of the early breakdown of the blood–brain barrier in Alzheimer’s disease models - Ka Ka Ting; Paul Coleman; Hani Jieun Kim; Yang Zhao; Jocelyne Mulangala; Ngan Ching Cheng; Wan Li; Dilini Gunatilake; Daniel M. Johnstone; Lipin Loo; G. Gregory Neely; Pengyi Yang; et al. (GeroScience, 2023)
Alzheimer’s disease (AD) is an age-related disease, with loss of integrity of the blood–brain barrier (BBB) being an early feature. Cellular senescence is one of the reported nine hallmarks of aging. Here, we show for the first time the presence of senescent cells in the vasculature in AD patients and mouse models of AD. Senescent endothelial cells and pericytes are present in APP/PS1 transgenic mice but not in wild-type littermates at the time of amyloid deposition. In vitro, senescent endothelial cells display altered VE-cadherin expression and loss of cell junction formation and increased permeability. Consistent with this, senescent endothelial cells in APP/PS1 mice are present at areas of vascular leak that have decreased claudin-5 and VE-cadherin expression confirming BBB breakdown. Furthermore, single cell sequencing of endothelial cells from APP/PS1 transgenic mice confirms that adhesion molecule pathways are among the most highly altered pathways in these cells. At the pre-plaque stage, the vasculature shows significant signs of breakdown, with a general loss of VE-cadherin, leakage within the microcirculation, and obvious pericyte perturbation. Although senescent vascular cells were not directly observed at sites of vascular leak, senescent cells were close to the leak area. Thus, we would suggest in AD that there is a progressive induction of senescence in constituents of the neurovascular unit contributing to an increasing loss of vascular integrity. Targeting the vasculature early in AD, either with senolytics or with drugs that improve the integrity of the BBB may be valid therapeutic strategies.

Life cycle assessment of greenhouse gas emission from the dairy production system — review - Arunasalam Singaravadivelan; Patil B. Sachin; S. Harikumar; Periyasamy Vijayakumar; M. V. Vindhya; F. M. Beegum Farhana; K. K. Rameesa; Joseph Mathew (Tropical Animal Health and Production, 2023)

Dealing with Environmental Fluctuations: Diversity of Potassium Uptake Systems Across the Three Domains of Life - Divya Rajagopal; Sudhir K. Sopory; M. K. Mathew (Journal of Plant Growth Regulation, 2023)

Integrative study of Permian coal-bearing horizons: biostratigraphy, palaeovegetation, and palaeoclimate in the South Karanpura Basin - Sanghamitra Pradhan; Shreerup Goswami; Neha Aggarwal; Runcie Paul Mathews; M. C. Manoj; S. Suresh K. Pillai; Siddharth Shekhar Pradhan (Environmental Geochemistry and Health, 2023)

Lower Permian Gondwana sequence of Rajhara (Daltonganj Coalfield), Damodar Basin, India: floristic and geochemical records and their implications on marine ingressions and depositional environment - Sankar Suresh Kumar Pillai; M. C. Manoj; Runcie Paul Mathews; Srikanta Murthy; Mrutyunjaya Sahoo; Anju Saxena; Anupam Sharma; Sanghamitra Pradhan; Suraj Kumar (Environmental Geochemistry and Health, 2023)

An overview of atmospheric aerosol and their effects on human health - Tanvir Arfin; Anupama M Pillai; Nikhila Mathew; Abha Tirpude; Roshani Bang; Pabitra Mondal (Environmental Science and Pollution Research, 2023)

Adherence to a Mediterranean-style Diet Is Associated with Decreased Depression and Anxiety Severity Regardless of Food Security Status: a Cross-sectional Study of College Freshmen - M. Alshahwan; A. Mathews; A. Ahrens; E. Triplett; L. LaMontagne; J. Doty; J. Colee (Journal of the Academy of Nutrition and Dietetics, 2023)

Higher Fat Intake Within a Vegan Diet Increases Skin Carotenoid Status in Patients at Risk for Cardiovascular Disease Participating in a Culinary Medicine Randomized Crossover Trial - A. Krenek; A. Courville; S. Chung; M. Aggarwal; A. Mathews (Journal of the Academy of Nutrition and Dietetics, 2023)

Adolescents’ Knowledge of Myplate as It Relates to Their Consumption of Fruits, Vegetables, and Whole Grains - M. Badolato; A. Mathews; K. Shelnutt; L. House; K. Chambers; J. Colee (Journal of the Academy of Nutrition and Dietetics, 2023)

Revelations on photosystem II, thermoluminescence, and artificial photosynthesis: a retrospective of Govindjee from fundamentals to applications - Mathew Veena; P. P. Sameena; Nair G. Sarath; Louis Noble; K. P. Raj Aswathi; M. S. Amritha; Riya Johnson; Joy M. Joel; K. S. Anjitha; Harvey J. M. Hou; Jos T. Puthur (Physiology and Molecular Biology of Plants, 2023)

Peroxisomal KAT2 (3-ketoacyl-CoA thiolase 2) gene has a key role in gingerol biosynthesis in ginger (Zingiber officinale Rosc.) - S. Sreeja; M. R. Shylaja; P. A. Nazeem; Deepu Mathew (Journal of Plant Biochemistry and Biotechnology, 2023)

John squire and endothelial glycocalyx structure: an unfinished story - Kenton P. Arkill; C. Charles Michel; Elizabeth V. M. Rider; Elise A. Wood; Mathew O. Small; Jennifer L. E. Brown; Abigail L. Kinnaird (Journal of Muscle Research and Cell Motility, 2023)
John Squire did not only produce leading works in the muscle field, he also significantly contributed to the vascular permeability field by ultrastructural analysis of the endothelial glycocalyx. Presented here is a review of his involvement in the field by his main collaborator C.C. Michel and his last postdoctoral researcher KP Arkill. We end on a reinterpretation of his work that arguably links to our current understanding of endothelial glycocalyx structure and composition predicting 6 glycosaminoglycans fibres per syndecan core protein, only achieved in the endothelium by dimerization.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Preparation and Characterization of 3D-Printed Dose-Flexible Printlets of Tenofovir Disoproxil Fumarate - Canberk Kayalar; Ziyaur Rahman; Eman M. Mohamed; Sathish Dharani; Tahir Khuroo; Nada Helal; Mathew A. Kuttolamadom; Mansoor A. Khan (AAPS PharmSciTech, 2023)

Short term water demand forecast modelling using artificial intelligence for smart water management - M Kavya; Aneesh Mathew; Padala Raja Shekar; Sarwesh P (Sustainable Cities and Society, 2023)

Pharmaceuticals in wastewater and their photocatalytic degradation using nano-enabled photocatalysts - Deborah Tebogo Ruziwa; Abimbola E. Oluwalana; Mathew Mupa; Lucas Meili; Rangabhashiyam Selvasembian; Matthew M. Nindi; Mika Sillanpaa; Willis Gwenzi; Nhamo Chaukura (Journal of Water Process Engineering, 2023)

Multi-instrument study of a spread-F event at Arecibo linked to solar wind variations - Salih Mehmed Bostan; Julio V. Urbina; John D. Mathews; Ross L. Dinsmore; Robert M. Robinson (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Effects of crustal assimilation on 238U-230Th disequilibria in continental arc settings - L.B. Kant; K.W.W. Sims; G.M. Yogodzinski; J.M. Garrison; J. Blichert-Toft; M. Reagan; C.L. Waters; T.P. Mathews; S.R. Scott; P.A. Mothes; M.L. Hall; P. Ramón; et al. (Geochimica et Cosmochimica Acta, 2023)

Isotopic niche of New Jersey terrapins suggests intraspecific resource partitioning, and little variability following a major hurricane - Mathew J. Denton; Kristen M. Hart; John Wnek; Sarah A. Moss; Harold W. Avery (Hydrobiologia, 2023)
Diamondback terrapins ( Malaclemys terrapin ) are sexually dimorphic generalist turtles that inhabit salt marshes and estuaries along the Atlantic and Gulf coasts of the United States. On October 29th, 2012, Hurricane Sandy made landfall in New Jersey, USA, directly impacting terrapin populations inhabiting central and southern Barnegat Bay. To examine potential food web mediated impacts to the terrapin population and their foraging dynamics we examined carbon and nitrogen stable isotope values collected from terrapin tissues (2011, 2015, 2019) and resource taxa (2015, 2019) within Barnegat Bay. Isotopic analysis revealed that mature females had lower carbon and higher nitrogen values than immature females and males with almost no isotopic niche overlap, whereas males and immature females had statistically similar values with overlapping niches. Terrapins and resources collected from island habitats contained higher carbon and nitrogen values than those from mainland habitats, with little overlap in niche between habitats. There were no significant temporal variations detected in either carbon or nitrogen values from terrapins between years, or within each habitat pre- and post-Hurricane Sandy. These findings suggest long-term terrapin foraging dynamics have remained relatively stable, signifying resilience to disturbance events within the study site.

Genome‐wide variant analyses reveal new patterns of admixture and population structure in Australian dingoes - Kylie M. Cairns; Mathew S. Crowther; Heidi G. Parker; Elaine A. Ostrander; Mike Letnic (Molecular Ecology, 2023)
Admixture between species is a cause for concern in wildlife management. Canids are particularly vulnerable to interspecific hybridisation, and genetic admixture has shaped their evolutionary history. Microsatellite DNA testing, relying on a small number of genetic markers and geographically restricted reference populations, has identified extensive domestic dog admixture in Australian dingoes and driven conservation management policy. But there exists a concern that geographic variation in dingo genotypes could confound ancestry analyses that use a small number of genetic markers. Here, we apply genome‐wide single‐nucleotide polymorphism (SNP) genotyping to a set of 402 wild and captive dingoes collected from across Australia and then carry out comparisons to domestic dogs. We then perform ancestry modelling and biogeographic analyses to characterise population structure in dingoes and investigate the extent of admixture between dingoes and dogs in different regions of the continent. We show that there are at least five distinct dingo populations across Australia. We observed limited evidence of dog admixture in wild dingoes. Our work challenges previous reports regarding the occurrence and extent of dog admixture in dingoes, as our ancestry analyses show that previous assessments severely overestimate the degree of domestic dog admixture in dingo populations, particularly in south‐eastern Australia. These findings strongly support the use of genome‐wide SNP genotyping as a refined method for wildlife managers and policymakers to assess and inform dingo management policy and legislation moving forwards.

Associations between a prenatal stress mixture and preschoolers’ temperament: Impact of race/ethnicity - Francheska M. Merced-Nieves; Elena Colicino; Michelle Bosquet Enlow; Brandon Goldson; Nicole Mathews; Bonnie Lerman; Robert O. Wright; Rosalind J. Wright (Neurotoxicology and Teratology, 2023)

Minerals profile and nutraceutical factors in landraces and hybrid varieties of rice: A comparison - Mathew Veena; Jos T. Puthur; Piotr Stępień; Hazem M. Kalaji (Food Bioscience, 2023)

A solar radiation and biosand filtration system for cooking and water treatment - H. Shollenberger; G. Mathews; M. Young; S. Clark; Y. Chen (International Journal of Environmental Science and Technology, 2023)

Genome wide identification and characterization of MATE family genes in mangrove plants - M. Shijili; Ravisankar Valsalan; Deepu Mathew (Genetica, 2023)

Development of DNA barcode-based PCR methodology to distinguish two sympatric species viz. Phlebotomus argentipes and Phlebotomus colabaensis (Diptera: Psychodidae: Phlebotominae) - P. A. Fathima; Harish Kumar Shah; P. M. Ajithlal; Jessu Mathew; N. Pradeep Kumar; Ashwani Kumar; Prasanta Saini (International Journal of Tropical Insect Science, 2023)

Concern about the human health implications of marine biodiversity loss is higher among less educated and poorer citizens: Results from a 14-country study in Europe - Sophie M. C. Davison; Mathew P. White; Sabine Pahl; Tim Taylor; Angel Borja; Oonagh McMeel; Paula Kellett; Bethany R. Roberts; Lora E. Fleming (Frontiers in Marine Science, 2023)
Introduction Marine biodiversity loss has direct and indirect effects on human health and wellbeing. Recent European data suggest that the public is aware of this, identifying marine biodiversity protection as its top research priority in terms of oceans and human health, rated higher than issues such as plastic, chemical, and microbial pollution. Methods The current study aimed to better understand key sociodemographic and personality predictors of concern about marine biodiversity loss and the desire for more research into marine biodiversity protection, in an attempt to support communication efforts targeting specific sectors in society. Data were drawn from nationally representative samples of 14 European countries (n = 14,167). Results Results show greater concern about marine biodiversity loss and support for more research into marine biodiversity protection by older adults, females, and individuals: (i) without (vs. with) a university degree; (ii) with lower (vs. middle) incomes; (iii) who identified as politically left-wing; (iv) who visited the coast more often; and (v) those with more open, agreeable and conscientious personalities. Discussion These results suggest that, although concern and research support are generally high among European citizens, policy makers and communicators need to take into consideration individual-level variation.

The relationship between single muscle fibre and voluntary rate of force development in young and old males - Benjamin E. Dalton; Nicole Mazara; Mathew I. B. Debenham; Derek P. Zwambag; Alex M. Noonan; Erin Weersink; Stephen H. M. Brown; Geoffrey A. Power (European Journal of Applied Physiology, 2023)

Natural organic matter flocculation behavior controls lead phosphate particle aggregation by mono- and divalent cations - Juntao Zhao; Riya A. Mathew; David S. Yang; Peter G. Vekilov; Yandi Hu; Stacey M. Louie (Science of The Total Environment, 2023)

Sea swimming and snorkeling in tropical coastal blue spaces and mental well-being: Findings from Indonesian island communities during the COVID-19 pandemic - Carya Maharja; Radisti A. Praptiwi; Bethany R. Roberts; Karyn Morrissey; Mathew P. White; Nuzulia M. Sari; Fauzan Cholifatullah; Jito Sugardjito; Lora E. Fleming (Journal of Outdoor Recreation and Tourism, 2023)

Comparison of the solid-state and submerged fermentation derived secretomes of hyper-cellulolytic Penicillium janthinellum NCIM 1366 reveals the changes responsible for differences in hydrolytic performance - Meena Sankar; Reshma M Mathew; Anoop Puthiyamadam; Athiraraj Sreeja-Raju; Meera Christopher; Digambar Vitthal Gokhale; Rajeev K. Sukumaran (Bioresource Technology, 2023)

Probing the influence of liquid nitrogen assisted chemical reduction on the nature of passivation layer, magnetic properties, and Cr (VI) remediation performance of nanoscale zero valent iron - Nibin K. Mathew; Rohith Vinod K; Theertharaman G; M. Navaneethan; S. Balakumar (Journal of Environmental Chemical Engineering, 2023)

Phenocam observed flowering anomaly of Rhododendron arboreum Sm. in Himalaya: a climate change impact perspective - Sudeep Chandra; Ankit Singh; Jincy Rachel Mathew; C. P. Singh; Mehul R. Pandya; Bimal K. Bhattacharya; Hitesh Solanki; M. C. Nautiyal; Rajesh Joshi (Environmental Monitoring and Assessment, 2022)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

First report of leaf blight of Indian spinach caused by Colletotrichum siamense in India - Sajeena Abdulmajeed; Mathew Deepu; M. K. Dhanya; John Jacob; P. Rawal; D. Jain; M. Elina; D. S. Nair; T. S. Peteti (Journal of Plant Pathology, 2022)

Production Optimization and In Vitro Evaluation of Anti-proliferative, Anti-oxidant and Anti-inflammatory Potential of the Antibacterial Peptide MFAP9 - Rekha Mol Kollakalnaduvil Raghavan; Manzur Ali Pannippara; Sapna Kesav; Abraham Mathew; Sarita G. Bhat; C. M. Rafeeq; K. K. Elyas (International Journal of Peptide Research and Therapeutics, 2022)

Social integration of translocated wildlife: a case study of rehabilitated and released elephant calves in northern Kenya - Shifra Z. Goldenberg; Stephen M. Chege; Nelson Mwangi; Ian Craig; David Daballen; Iain Douglas-Hamilton; Nadine Lamberski; Moses Lenaipa; Reuben Lendira; Colman Lesowapir; Lekilia P. Lokooria; Mathew Mutinda; et al. (Mammalian Biology, 2022)
Conservation translocations have the potential to strengthen populations of threatened and endangered species, but facilitating integration of translocated individuals with resident populations remains a substantial challenge. Developing functional social relationships like cooperative partnerships or establishing clear dominance hierarchies may be critical to integration of released individuals. Developing such relationships has not received much attention in translocation research, especially for long-lived, socially complex animals for which establishment and navigation of social environments is often a lengthy process that requires sustained monitoring to understand. Here, we present a case study of the social associations of African savannah elephant ( Loxodonta africana ) calves that have been rehabilitated and released into a fenced wildlife sanctuary in northern Kenya with a resident population of elephants. We use focal follows of interactions pre-release and GPS tracking post-release to quantify social associations of calves with each other and with resident elephants at the release site. We demonstrate how this approach supports translocation monitoring by capturing temporal trends in social patterns within and between release cohorts and among released elephants and wild elephants already resident at the site during a transitional soft release period. Our results show that initial post-release social behavior of rehabilitated calves is related to histories of interaction with familiar individuals and cohort membership and that released calves increased their associations with residents over time. This information provides new behavioral insights for guiding elephant release projects, like the strength of relationships within and among release cohorts, the time to integration with the resident population, and the occurrence and increased incidence of societal fission–fusion. Further, this study provides an example of the utility of animal behavior research to achieve and assess progress towards conservation objectives, and to develop monitoring tools for conservation managers.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Right Heart Morphology of Candidate Patients for Transcatheter Tricuspid Valve Interventions - Omar K. Khalique; Vladimir Jelnin; Andreas Hueske; Mathew Lawlor; Martin B. Leon; Susheel K. Kodali; Deniz Akkoc; Eriq Pettway; Rebecca T. Hahn; Nadira B. Hamid; Isaac George; Amisha Patel; et al. (Cardiovascular Engineering and Technology, 2022)
Purpose This study quantitatively evaluated the phasic right heart morphology of candidate patients for a transcatheter tricuspid valve intervention (N=32) and of subjects with trace to no tricuspid regurgitation ( N = 14). Methods Cardiac computed tomography angiography (CCTA) and transthoracic/transesophageal echocardiography (TTE/TEE) images were analyzed using dedicated research and clinical software. Using CCTA, the phasic right atrial and ventricular volumes, annulus dimensions, annulus-to-right coronary artery (RCA) distances, circumferential topography of the annular tissue shelf, vena cava dimensions (inferior and superior), vena cava positions, axis angles, and annular excursions were quantified. Using TTE/TEE, leaflet geometry, regurgitation, hemodynamics, and heart function were quantified. Measurements within and between groups were quantitatively compared with regression analyses to explore relationships between right heart features. Results The phasic position and orientation of the vena cava and the circumferential topography of the annular tissue shelf were quantitatively presented for the first time. The candidate patient group exhibited greater chamber dimensions, enlarged vena cava, distended vena cava positions, positional shallowing of the annular tissue shelf, geometric annular distortion, leaflet distention, moderate or greater regurgitation, and impaired ventricular function. Atrial volume correlated strongly with directional vena cava positions as well as with annular dimensions. Annulus-to-RCA distances and annular excursions were comparable between groups. Conclusions This study provides new and further insight to the right heart morphology and functional characteristics of candidate patients for a transcatheter tricuspid valve intervention. These data provide a platform from which these patients can continue to be better understood for further improving transcatheter system design and use.

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

Coconut Sugar- a Potential Storehouse of Nutritive Metabolites, Novel Bio-products and Prospects - K. B. Hebbar; S. V. Ramesh; D. K. Ghosh; P. P. Shameena Beegum; R. Pandiselvam; M. R. Manikantan; A. C. Mathew (Sugar Tech, 2022)

Altered Sleep Duration and Poor Quality of Sleep Among Pharmacy Students Amidst COVID-19 Lockdown: A South-Indian Study - P. Vaidehi Bhat; Sophia M. George; Sharad Chand; Kauma Kurian; Emy Susan Roy; Greeshma Mathew; R. Prajnashree; Haritha S. Nath; Akshara Theresa Babu; Jeffrey C. Reist (Sleep and Vigilance, 2022)

Evaluation of okra genotypes against yellow vein mosaic disease (YVMD) - Alphy Mathew; T. Pradeepkumar; J. S. Minimol; K. Anita Cherian; M. Sangeeta Kutty (Indian Phytopathology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Epiphytism, diseases and grazing in seaweed aquaculture: A comprehensive review - Durga Prasad Behera; Kapilkumar N. Ingle; Doniya Elze Mathew; Asmita Dhimmar; Harshal Sahastrabudhe; Sunil Kumar Sahu; M. Gobala Krishnan; Pramod. B. Shinde; M. Ganesan; Vaibhav. A. Mantri (Reviews in Aquaculture, 2022)
Seaweeds are macroscopic forms of phylogenetically diverse assemblage of marine algae that grow in oceans, thriving among profoundly harsh environmental conditions. They are cultivated in many maritime nations primarily for edible applications; besides hydrocolloid extraction is the second largest domain of utility for this renewable biomass. The farming practices have been traditionally evolved in different Southeast Asian countries. Nevertheless, advancement in the knowledge about their life‐history traits and control over reproduction has paved ways for commencement of large‐scale commercial farming. Food and Agriculture Organisation of United Nations reported the availability of 35.8 million tons of seaweed biomass globally of which 97% accounted for farming. Although cultivation is on the rise due to relevant to social gains, epiphytic infestation, diseases and grazing have been identified as leading causes that result in substantially lower yield, deteriorated quality of product and skewed economics. Epiphytes may considerably impact the interaction of seaweed hosts with other beneficial communities also. Epidemiological studies in natural seaweed populations are scarce and this makes the understanding of the cross‐talk involving host specificity, and their role obscure. An overview of the diversity of epiphytes, understanding of mechanism of action, factors responsible, chemistry behind their interaction will help in deciphering the solutions to overcome infestation. A comprehensive report of seaweed epiphytism, diseases and grazing from the aspects of host–epiphyte interaction and their resultant consequences is presented along with the studies on economic impacts. The role of multi‐omics approaches in delineating seaweed epiphytic interactions is also included.

First report of fruit rot of jackfruit caused by Athelia rolfsii in India - Abdulmajeed Sajeena; Deepu Mathew; Jacob John; M. K. Dhanya; K. Sushitha; P. Ruby Nahan (Journal of Plant Pathology, 2022)

Total hip replacement monitoring: numerical models for the acoustic emission technique - Remya Ampadi Ramachandran; Christine Lee; Lu Zhang; Supriya M. H; Divya Bijukumar; P. Srinivasa Pai; Kharma Foucher; Sheng-Wei Chi; Didem Ozevin; Mathew T. Mathew (Medical & Biological Engineering & Computing, 2022)

Internal seiches as drivers of fish depth use in lakes - Jill L. Brooks; Jonathan D. Midwood; Adam Smith; Steven J. Cooke; Bryan Flood; Christine M. Boston; Patricia Semecsen; Susan E. Doka; Mathew G. Wells (Limnology and Oceanography, 2022)
Inland temperate lakes undergo various physical processes, such as thermal stratification, that dictate the spatial availability of suitable temperature and dissolved oxygen conditions. Here, we use intensive limnological monitoring and acoustic telemetry transmitters implanted in wild fish to document the magnitude and frequency of thermocline deflection events (i.e., wind driven internal seiches that lead to upwelling of hypoxic hypolimnetic water) and their influence on freshwater fish depth use in a coastal embayment of Lake Ontario. The embayment experienced around 100 internal seiche events during a 3‐month period and tracking of walleye ( Stizostedion vitreus ) vertical positions in the water column showed clear trends of avoidance of low dissolved oxygen. Quantile regression showed a significant correlation between walleye vertical position and the depth of the 3, 4, and 5 mg L −1 oxyclines, with the 3 mg L −1 oxycline having the largest effect. Upwellings of the hypoxic hypolimnion forced walleye to use the water column above these fluctuating oxyclines (5 th percentile, p −1 oxycline. Understanding how fish respond to upwelling events (both temperature and oxygen) is important for fisheries assessment, management, and habitat restoration planning as there is clear avoidance of suboptimal oxygen conditions and sampling in the overcrowded fringes of these low‐oxygen zones could artificially inflate population estimates.

Molecular analysis of aroma gene (BADH2) in Biriyanicheera: a tropical aromatic rice genotype from Kerala, India - M. Veerabhadraswamy; P. Sindhumole; Deepu Mathew; M. R. Shylaja; Jiji Joseph; Rehna Augustine; Donald James (Molecular Biology Reports, 2022)

Immunoinformatics prediction of potential immunodominant epitopes from human coronaviruses and association with autoimmunity - Shilu Mathew; Aisha D. Fakhroo; Maria Smatti; Asmaa A. Al Thani; Hadi M. Yassine (Immunogenetics, 2022)

Operationalizing and empirically identifying populations trapped in place by climate and environmental stressors in Mexico - Jack DeWaard; Lori M. Hunter; Mason C. Mathews; Esteban J. Quiñones; Fernando Riosmena; Daniel H. Simon (Regional Environmental Change, 2022)

Potential of Microrhizomes for In Vitro Gingerol and Shogaol Synthesis in Ginger (Zingiber officinale Rosc.) - Manjusha Rani; M. R. Shylaja; Deepu Mathew; D. Girija; M. Asha Shankar; P. Sureshkumar; C. Beena (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Glyphosate residues alter the microbiota of a perennial weed with a minimal indirect impact on plant performance - S. Ramula; S. A. Mathew; A. Kalske; R. Nissinen; K. Saikkonen; M. Helander (Plant and Soil, 2022)
Purpose In cold climates, glyphosate residues may linger in soils, with effects on plant–microbe interactions and, consequently, plant performance. Here, we explore the influence of glyphosate residues on the endophytic microbiota (bacteria and fungi) and performance of the perennial nitrogen-fixing weed Lupinus polyphyllus . Methods In a common garden, we grew plants from six populations of L. polyphyllus in glyphosate-treated or untreated control soils, with or without additional phosphorus. We sampled plant microbiota (leaves, roots, nodules) and assessed plant performance based on six traits: height, retrogression probability (i.e. shrinkage), biomass, root:shoot ratio, nodule number, and nodule viability. Results The richness of plant endophytic microbial communities was determined by soil phosphorus level rather than by glyphosate treatment. However, for bacteria, the composition of these communities differed between glyphosate-treated and control soils across plant tissue types; no difference was observed for fungi. The plant bacterial communities in both soil types were dominated by potential nitrogen-fixing bacteria belonging to family Bradyrhizobiaceae, and particularly so in glyphosate-treated soils. Overall, though, these changes in plant bacterial communities had a minor effect on plant performance: the only difference we detected was that the probability of retrogression was occasionally higher in glyphosate-treated soils than in control soils. Conclusion Our findings indicate that glyphosate-based herbicides, when applied at the recommended frequency and concentration, may not have critical effects on the growth of short-lived weeds after the safety period has passed; however, the endophytic microbiota of such weeds may experience longer-lasting shifts in community structure.

Effectiveness of Site-Specific Management Practices on the Amelioration of Soil Acidity in the Coconut Growing Entisol and Ultisol of Humid Tropics - Jeena Mathew; A. Abdul Haris; S. Indhuja; V. Krishnakumar; K. M. Nair; Ravi Bhat; K. S. Anil Kumar (Journal of Soil Science and Plant Nutrition, 2022)

Modeling Impacts of Submersed Aquatic Vegetation on Sediment Dynamics Under Storm Conditions in Upper Chesapeake Bay - Mathew M. Biddle; Cindy M. Palinkas; Lawrence P. Sanford (Estuaries and Coasts, 2022)

Point of Care Blood Gas and Electrolyte Analysis in Anesthetized Olive Baboons (Papio anubis) in a Field Setting - Maureen W. Kamau; James M. Hassell; Ellie L. Milnes; Lee-Ann C. Hayek; Mathew M. Mutinda; Roi Harel; Akiko Matsumoto-Oda; Jennifer H. Yu; Dawn Zimmerman; Margaret Crofoot; Suzan Murray (International Journal of Primatology, 2021)

Evaluation of the Effectiveness of Newer Helmet Designs with Emergent Shell and Padding Technologies Versus Older Helmet Models for Preserving White Matter Following a Season of High School Football - Jed A. Diekfuss; Weihong Yuan; Jonathan A. Dudley; Christopher A. DiCesare; Matthew B. Panzer; Thomas M. Talavage; Eric Nauman; Scott Bonnette; Alexis B. Slutsky-Ganesh; Joseph Clark; Manish Anand; Mekibib Altaye; et al. (Annals of Biomedical Engineering, 2021)

Flood impact assessment using field investigations and post-flood survey - Aleena Elsa Mathew; S Sujith Kumar; G Vivek; M Iyyappan; R Karthikaa; P Dinesh Kumar; S K Dash; G Gopinath; Tune Usha (Journal of Earth System Science, 2021)

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Coral reef resilience differs among islands within the Gulf of Mannar, southeast India, following successive coral bleaching events - K. Diraviya Raj; Greta S. Aeby; G. Mathews; Gareth J. Williams; Jamie M. Caldwell; R. L. Laju; M. Selva Bharath; P. Dinesh Kumar; A. Arasamuthu; N. Gladwin Gnana Asir; Lisa M. Wedding; Andrew J. Davies; et al. (Coral Reefs, 2021)

Taphonomy of an excavated striped hyena (Hyaena hyaena) den in Arabia: implications for paleoecology and prehistory - Mathew Stewart; Eric Andrieux; Richard Clark-Wilson; Nils Vanwezer; James Blinkhorn; Simon J. Armitage; Abdulaziz al Omari; Badr Zahrani; Mesfer Alqahtani; Mahmoud Al-Shanti; Iyad Zalmout; Yahya S. A. Al-Mufarreh; et al. (Archaeological and Anthropological Sciences, 2021)
Studies of modern carnivore accumulations of bone (i.e., neo-taphonomy) are crucial for interpreting fossil accumulations in the archaeological and paleontological records. Yet, studies in arid regions have been limited in both number and detailed taphonomic data, prohibiting our understanding of carnivore bone-accumulating and -modifying behavior in dry regions. Here, we present a taphonomic analysis of an impressive carnivore-accumulated bone assemblage from the Umm Jirsan lava tube in the Harrat Khaybar region, Saudi Arabia. The size and composition of the bone accumulation, as well as the presence of hyena skeletal remains and coprolites, suggest that the assemblage was primarily accumulated by striped hyena ( Hyaena hyaena ). Our findings (1) identify potentially useful criteria for distinguishing between accumulations generated by different species of hyenas; (2) emphasize the need for neo-taphonomic studies for capturing the full variation in carnivore bone-accumulating and modifying behavior; (3) suggest that under the right settings, striped hyena accumulations can serve as good proxies for (paleo)ecology and livestock practices; and (4) highlight the potential for future research at Umm Jirsan, as well as at the numerous nearby lava tube systems. We encourage continued neo-taphonomic efforts in regions important in human prehistory, particularly in arid zones, which have received little research attention.

Simulation of interannual relationship between the Atlantic zonal mode and Indian summer monsoon in CFSv2 - Vijay Pottapinjara; Mathew Koll Roxy; M. S. Girishkumar; Karumuri Ashok; Sudheer Joseph; M. Ravichandran; R. Murtugudde (Climate Dynamics, 2021)

Epidemiological, molecular, and clinical features of rotavirus infections among pediatrics in Qatar - Shilu Mathew; Khalid Al Ansari; Asmaa A. Al Thani; Hassan Zaraket; Hadi M. Yassine (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Morphological variations of wheat (Triticum aestivum L. em. Thell.) under variable ethyl methanesulphonate mutagenesis - Boluwatife M. OlaOlorun; Hussein Shimelis; Mark Laing; Isack Mathew (Cereal Research Communications, 2021)

Intestinal histological alterations in farmed red-bellied pacu Piaractus brachypomus (Characiformes: Serrasalmidae) heavily infected by roundworms - Ruben C. Cuadros; Norma L. S. Rivadeneyra; Anai Flores-Gonzales; Omar Mertins; Jose C.O. Malta; M. Enrique Serrano-Martínez; Patrick D. Mathews (Aquaculture International, 2021)

Development of Groundnut Meal Incorporated Rice–Corn Flour Based Extruded Snack-Food - Pravin M. Ganorkar; Marmik V. Shah; Jaydeep C. Kamariya; Yohanah Mathew (Agricultural Research, 2021)

Pinpointing Drivers of Extirpation in Sea Snakes: A Synthesis of Evidence From Ashmore Reef - Ruchira Somaweera; Vinay Udyawer; Michael L. Guinea; Daniela M. Ceccarelli; Rohan H. Clarke; Michelle Glover; Mathew Hourston; John Keesing; Arne Redsted Rasmussen; Kate Sanders; Richard Shine; Damian P. Thomson; et al. (Frontiers in Marine Science, 2021)
Over the past decade, vertebrate populations globally have experienced significant declines in distribution and abundance. Understanding the reasons behind these population declines is the first step in implementing appropriate management responses to improve conservation outcomes. Uncovering drivers of extirpation events after the fact, however, requires a careful forensic approach to prevent similar declines elsewhere. The once abundant and species-rich sea snake fauna of Ashmore Reef Marine Park, in the Timor Sea, collapsed dramatically in the early 2000s. No such decline has occurred on surrounding reefs. We synthesise the evidence for this collapse and the subsequent slow recovery and evaluate the plausibility of potential drivers for the declines, as well as provide evidence against certain explanations that have been proposed in the past. Our systematic review shows that of seven possible hypotheses considered, at least three are credible and require additional information: (1) stochastic environmental events may have increased the snakes’ susceptibility to pathogens, (2) a resurgence in the abundance of top predators may have induced a localised change in trophic structure, and (3) an acute increase in local boat traffic may have had negative physical impacts. One or more of these factors, possibly acting in combination with as yet other unidentified factors, is the most plausible explanation for the precipitous decline in sea snake populations observed. Based on this position, we identify future research directions with a focus on addressing critical gaps in knowledge to inform and prioritise future management actions.

Is Pacific white shrimp (Penaeus vannamei) farming in India sustainable? A multidimensional indicators-based assessment - M. Kumaran; M. Sundaram; Shijo Mathew; P. R. Anand; T. K. Ghoshal; P. Kumararaja; R. Anandaraja; Shyne Anand; K. K. Vijayan (Environment, Development and Sustainability, 2021)

A system for rapid gene introgression into cassava immature leaves and subsequent recovery of transformed lines - Easter D. Syombua; Mark O. Adero; Wilton M. Mbinda; Christine N. Wanyonyi; Mathew P. Ngugi; Richard O. Oduor (Plant Biotechnology Reports, 2021)

The Contrasting Ecology of Free-Living Nematodes in Macrotidal and Microtidal Estuaries - Richard M. Warwick; Mathew Hourston; James R. Tweedley; Ian C. Potter (Estuaries and Coasts, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Temporal stability vs. community matrix measures of stability and the role of weak interactions - Amy L. Downing; Craig Jackson; Claire Plunkett; Jayne Ackerman Lockhart; Shannon M. Schlater; Mathew A. Leibold (Ecology Letters, 2020)
Relationships between different measures of stability are not well understood in part because empiricists and theoreticians tend to measure different aspects and most studies only explore a single form of stability. Using time‐series data from experimental plankton communities, we compared temporal stability typically measured by empiricists (coefficient of variation in biomass) to stability measures typically measured by theoreticians derived from the community matrix (asymptotic resilience, initial resilience and intrinsic stochastic invariability) using first‐order multivariate autoregressive models (MAR). Community matrices were also used to derive estimates of interaction strengths between plankton groups. We found no relationship between temporal stability and stability measures derived from the community matrix. Weaker interaction strengths were generally associated with higher stability for community matrix measures of stability, but were not consistently associated with higher temporal stability. Temporal stability and stability measures derived from the community matrix stability appear to represent different aspects of stability reflecting the multi‐dimensionality of stability.

Exploring nationality and social identity to explain attitudes toward conservation actions in the United States and Australia - Lily M. van Eeden; Kristina Slagle; Thomas M. Newsome; Mathew S. Crowther; Christopher R. Dickman; Jeremy T. Bruskotter (Conservation Biology, 2020)
Understanding human attitudes toward wildlife management is critical to implementing effective conservation action and policy. Understanding the factors that shape public attitudes toward different wildlife management actions is limited, however, which can result in unpredictable public responses to interventions. We drew on comparisons between residents of 2 countries on separate continents to explore differences in attitudes toward wildlife management and determine factors important in shaping these attitudes. We surveyed representative publics via market research panels in Australia ( n = 881 respondents) and the United States ( n = 1287). We applied a social‐identity approach and demography to identify factors that explained variance between responses about wildlife management. We compared responses between countries overall and within subgroups of respondents who strongly identified as environmentalists, animal rights activists, wildlife conservation advocates, and farmers. We created aggregate scores for the management‐related response items per respondent and used regression analyses to identify the relative importance of country, identity, age, and gender in explaining variance between responses. These factors accounted for 15.3% of variance among responses. Australians overall were generally more accepting of lethal wildlife management actions than U.S. respondents. Differences in national attitudes reflected differences between United States and Australian wildlife management and policy, highlighting the importance of understanding social attitudes in shaping conservation policy. Identifying as a farmer followed by identifying as an animal rights activist most shaped attitudes toward wildlife management. Identity‐related conflicts could be initiated or exacerbated by conservation interventions that fail to consider identity‐related processes.

Between a Reef and a Hard Place: Capacity to Map the Next Coral Reef Catastrophe - Sharyn M. Hickey; Ben Radford; Chris M. Roelfsema; Karen E. Joyce; Shaun K. Wilson; Daniel Marrable; Kathryn Barker; Mathew Wyatt; Harriet N. Davies; Javier X. Leon; John Duncan; Thomas H. Holmes; et al. (Frontiers in Marine Science, 2020)

Oleoyl alanine (HU595): a stable monomethylated oleoyl glycine interferes with acute naloxone precipitated morphine withdrawal in male rats - Samantha M. Ayoub; Reem Smoum; Mathew Farag; Harkirat Atwal; Stephen A. Collins; Erin M. Rock; Cheryl L. Limebeer; Fabiana Piscitelli; Fabio Arturo Iannotti; Aron H. Lichtman; Francesco Leri; Vincenzo Di Marzo; et al. (Psychopharmacology, 2020)

Formulation Optimization of Selective Laser Sintering 3D-Printed Tablets of Clindamycin Palmitate Hydrochloride by Response Surface Methodology - Eman M. Mohamed; Sogra F. Barakh Ali; Ziyaur Rahman; Sathish Dharani; Tanil Ozkan; Mathew A. Kuttolamadom; Mansoor A. Khan (AAPS PharmSciTech, 2020)

Holocene coastal change at Luce Bay, South West Scotland - David E. Smith; Richard M. Tipping; Jason T. Jordan; Mathew Blackett (Journal of Quaternary Science, 2020)
Coastal change during the Mid‐ to Late Holocene at Luce Bay, South West Scotland, is examined using morphological, stratigraphic and biostratigraphical techniques supported by radiocarbon dating. Deglaciation left extensive sediments, providing a source for depositional coastal landforms. Glacio‐isostatic uplift resulted in the registration of evidence for former relative sea levels (RSLs), which support the pattern of Holocene RSL change for the northern Irish Sea as determined by shoreline‐based Gaussian trend surface models. The rate of RSL rise was rapid from before ca . 8600 to ca . 7800 cal a bp , but then slowed, changing by ca . 4400 cal a bp RSL was falling towards present levels. As these changes were taking place, coastal barriers developed and dunes formed across them. In the West of the Bay, a lagoon forming to landward of the barriers and dunes acted as a sediment sink for dune sand. Changes in the coastal landscape influenced the occupation of the area by early human societies. This study illustrates the value of combining an understanding of process geomorphology, RSL and archaeology in studies of coastal change.

Formulation, Optimization and Evaluation of Novel Ultra-deformable Vesicular Drug Delivery System for an Anti-fungal Drug - Devika Nayak; Roshan M. Tawale; Jesil Mathew Aranjani; Vamshi Krishna Tippavajhala (AAPS PharmSciTech, 2020)

Cloning and characterization of Myo-inositol phosphate synthase gene (dlMIPS) and analysis of the putative structure of the enzyme responsible for the accumulation of anti-nutrient phytate in dolichos bean (Dolichos lablab L.) - Sreedevi Jagal Kishore; Deepu Mathew; M. R. Shylaja; Rose Mary Francies; R. Sujatha (Plant Physiology Reports, 2020)

Nanoparticles and its biomedical applications in health and diseases: special focus on drug delivery - Nuzhat Zahin; Raihanatul Anwar; Devesh Tewari; Md. Tanvir Kabir; Amin Sajid; Bijo Mathew; Md. Sahab Uddin; Lotfi Aleya; Mohamed M. Abdel-Daim (Environmental Science and Pollution Research, 2020)

Changes in future rainfall extremes over Northeast Bangladesh: A Bayesian model averaging approach - Abul Basher; A. K. M. Saiful Islam; Mathew A. Stiller‐Reeve; Pao‐Shin Chu (International Journal of Climatology, 2020)
In this paper, we used a Bayesian model averaging (BMA) approach to analyse the changes in rainfall extremes in the periods 2041–2070 and 2071–2099 over northeast Bangladesh as a consequence of climate change. Climate change over this region could potentially impact agricultural production, water resources management, and the overall economy of the country. We used six regional climate models (RCMs) over the Coordinated Regional Downscaling Experiment South Asia domain. We used one medium stabilization scenario (RCP4.5) and one high‐emission scenario (RCP8.5) for projecting the extreme rainfall indices. A multi‐model ensemble mean was generated using the BMA approach. The BMA mean is a weighted average related to each RCM's predictive skill during the training period. Most of the rainfall extremes are expected to increase in both pre‐monsoon (March–May) and monsoon (June–September) seasons in the future compared with baseline (1976–2005). The average pre‐monsoon rainfall of the study area is projected to increase by 12.93 and 18.42% under RCP4.5 and 18.18 and 23.85% under RCP8.5 for the periods 2041–2070 and 2071–2099, respectively. The average monsoon rainfall of the study area is projected to increase by 4.96 and 2.27% under RCP4.5 and 6.56 and 6.40% under RCP8.5 for the periods 2041–2070 and 2071–2099, respectively. All the extreme indices except consecutive wet day are expected to change significantly at the 95% confidence level during the pre‐monsoon season. The study area will potentially be subjected to more frequent floods in the future both in pre‐monsoon and monsoon seasons as a consequence of climate change. Notably, the intensity and the magnitude of flash flooding in the pre‐monsoon season are expected to increase more in the future because the increase in extreme indices is more significant during that season.

Characterising the biophysical, economic and social impacts of soil carbon sequestration as a greenhouse gas removal technology - Alasdair J. Sykes; Michael Macleod; Vera Eory; Robert M. Rees; Florian Payen; Vasilis Myrgiotis; Mathew Williams; Saran Sohi; Jon Hillier; Dominic Moran; David A. C. Manning; Pietro Goglio; et al. (Global Change Biology, 2020)
To limit warming to well below 2°C, most scenario projections rely on greenhouse gas removal technologies (GGRTs); one such GGRT uses soil carbon sequestration (SCS) in agricultural land. In addition to their role in mitigating climate change, SCS practices play a role in delivering agroecosystem resilience, climate change adaptability and food security. Environmental heterogeneity and differences in agricultural practices challenge the practical implementation of SCS, and our analysis addresses the associated knowledge gap. Previous assessments have focused on global potentials, but there is a need among policymakers to operationalise SCS. Here, we assess a range of practices already proposed to deliver SCS, and distil these into a subset of specific measures. We provide a multidisciplinary summary of the barriers and potential incentives towards practical implementation of these measures. First, we identify specific practices with potential for both a positive impact on SCS at farm level and an uptake rate compatible with global impact. These focus on: (a) optimising crop primary productivity (e.g. nutrient optimisation, pH management, irrigation); (b) reducing soil disturbance and managing soil physical properties (e.g. improved rotations, minimum till); (c) minimising deliberate removal of C or lateral transport via erosion processes (e.g. support measures, bare fallow reduction); (d) addition of C produced outside the system (e.g. organic manure amendments, biochar addition); (e) provision of additional C inputs within the cropping system (e.g. agroforestry, cover cropping). We then consider economic and non‐cost barriers and incentives for land managers implementing these measures, along with the potential externalised impacts of implementation. This offers a framework and reference point for holistic assessment of the impacts of SCS. Finally, we summarise and discuss the ability of extant scientific approaches to quantify the technical potential and externalities of SCS measures, and the barriers and incentives to their implementation in global agricultural systems.

Morphological and molecular intervention in identifying Phytophthora spp. causing leaf and nut fall in nutmeg (Myristica fragrans Houtt.) - M. Anandaraj; Sally K. Mathew; Santhosh J. Eapen; J. Cissin; B. Rosana; R. Suseela Bhai (European Journal of Plant Pathology, 2020)

Geographic hot spots of dingo genetic ancestry in southeastern Australia despite hybridisation with domestic dogs - Kylie M. Cairns; Bradley J. Nesbitt; Shawn W. Laffan; Mike Letnic; Mathew S. Crowther (Conservation Genetics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Melatonin in Alzheimer’s Disease: A Latent Endogenous Regulator of Neurogenesis to Mitigate Alzheimer’s Neuropathology - Md. Farhad Hossain; Md. Sahab Uddin; G. M. Sala Uddin; Dewan Md. Sumsuzzman; Md. Siddiqul Islam; George E. Barreto; Bijo Mathew; Ghulam Md Ashraf (Molecular Neurobiology, 2019)

Environmental friendly synthesis of zinc oxide nanoparticles and estimation of its larvicidal activity against Aedes aegypti - S. M. Roopan; R. S. Mathew; S. S. Mahesh; D. Titus; K. Aggarwal; N. Bhatia; K. I. Damodharan; K. Elumalai; J. J. Samuel (International Journal of Environmental Science and Technology, 2019)

Urbanization impacts apex predator gene flow but not genetic diversity across an urban‐rural divide - Daryl R. Trumbo; Patricia E. Salerno; Kenneth A. Logan; Mathew W. Alldredge; Roderick B. Gagne; Christopher P. Kozakiewicz; Simona Kraberger; Nicholas M. Fountain‐Jones; Meggan E. Craft; Scott Carver; Holly B. Ernest; Kevin R. Crooks; et al. (Molecular Ecology, 2019)
Apex predators are important indicators of intact natural ecosystems. They are also sensitive to urbanization because they require broad home ranges and extensive contiguous habitat to support their prey base. Pumas ( Puma concolor ) can persist near human developed areas, but urbanization may be detrimental to their movement ecology, population structure, and genetic diversity. To investigate potential effects of urbanization in population connectivity of pumas, we performed a landscape genomics study of 130 pumas on the rural Western Slope and more urbanized Front Range of Colorado, USA. Over 12,000 single nucleotide polymorphisms (SNPs) were genotyped using double‐digest, restriction site‐associated DNA sequencing (ddRADseq). We investigated patterns of gene flow and genetic diversity, and tested for correlations between key landscape variables and genetic distance to assess the effects of urbanization and other landscape factors on gene flow. Levels of genetic diversity were similar for the Western Slope and Front Range, but effective population sizes were smaller, genetic distances were higher, and there was more admixture in the more urbanized Front Range. Forest cover was strongly positively associated with puma gene flow on the Western Slope, while impervious surfaces restricted gene flow and more open, natural habitats enhanced gene flow on the Front Range. Landscape genomic analyses revealed differences in puma movement and gene flow patterns in rural versus urban settings. Our results highlight the utility of dense, genome‐scale markers to document subtle impacts of urbanization on a wide‐ranging carnivore living near a large urban center.

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Implication of salt stress induces changes in pigment production, antioxidant enzyme activity, and qRT-PCR expression of genes involved in the biosynthetic pathway of Bixa orellana L. - M. Sankari; H. Hridya; P. Sneha; C. George Priya Doss; J. Godwin Christopher; Jill Mathew; Hatem Zayed; Siva Ramamoorthy (Functional & Integrative Genomics, 2019)

Pleistocene climate changes, and not agricultural spread, accounts for range expansion and admixture in the dominant grassland species Lolium perenne L. - José Luis Blanco‐Pastor; Stéphanie Manel; Philippe Barre; Anna M. Roschanski; Evelin Willner; Klaus J. Dehmer; Mathew Hegarty; Hilde Muylle; Tom Ruttink; Isabel Roldán‐Ruiz; Thomas Ledauphin; Abraham Escobar‐Gutiérrez; et al. (Journal of Biogeography, 2019)
Aim Grasslands have been pivotal in the development of herbivore breeding since the Neolithic and still represent the most widespread agricultural land use across Europe. However, it remains unclear whether the current large‐scale genetic variation of plant species found in natural grasslands of Europe is the result of human activities or natural processes. Location Europe. Taxon Lolium perenne L. (perennial ryegrass). Methods We reconstructed the phylogeographic history of L. perenne , a dominant grassland species, using 481 natural populations, including 11 populations of closely related taxa. We combined Genotyping‐by‐Sequencing (GBS) and pool‐Sequencing (pool‐Seq) to obtain high‐quality allele frequency calls of ~500 k SNP loci. We performed genetic structure analyses and demographic reconstructions based on the site frequency spectrum (SFS). We additionally used the same genotyping protocol to assess the genomic diversity of a set of 32 cultivars representative of the L. perenne cultivars widely used for forage purposes. Results Expansion across Europe took place during the Würm glaciation (12–110 kya), a cooling period that decreased the dominance of trees in favour of grasses. Splits and admixtures in L. perenne fit historical climate changes in the Mediterranean basin. The development of agriculture in Europe (7–3.5 kya), that caused an increase in the abundance of grasslands, did not have an effect on the demographic patterns of L. perenne . We found that most modern cultivars are closely related to natural diversity from north‐western Europe. Thus, modern cultivars do not represent the wide genetic variation found in natural populations. Main conclusions Demographic events in L. perenne can be explained by the changing climatic conditions during the Pleistocene. Natural populations maintain a wide genomic variability at continental scale that has been minimally exploited by recent breeding activities. This variability constitutes valuable standing genetic variation for future adaptation of grasslands to climate change, safeguarding the agricultural services they provide.

Employing Measurers of Spatial Distribution of Carbon Storage in Periyar Tiger Reserve, Southern Western Ghats, India - Shiju Chacko; C. Ravichandran; S. M. Vairavel; John Mathew (Journal of Geovisualization and Spatial Analysis, 2019)

Stable Isotope Analysis Enhances Our Understanding of Diamondback Terrapin (Malaclemys terrapin) Foraging Ecology - Mathew J. Denton; Amanda W. J. Demopoulos; John D. Baldwin; Brian J. Smith; Kristen M. Hart (Estuaries and Coasts, 2019)

Variance components and heritability of traits related to root: shoot biomass allocation and drought tolerance in wheat - I. Mathew; H. Shimelis; L. Mwadzingeni; R. Zengeni; M. Mutema; V. Chaplot (Euphytica, 2018)

Future Directions in the Research and Management of Marine Snakes - Vinay Udyawer; Peter Barnes; Xavier Bonnet; François Brischoux; Jenna M. Crowe-Riddell; Blanche D’Anastasi; Bryan G. Fry; Amber Gillett; Claire Goiran; Michael L. Guinea; Harold Heatwole; Michelle R. Heupel; et al. (Frontiers in Marine Science, 2018)

Coated-Platelet Trends Predict Short-Term Clinical OutcomeAfter Subarachnoid Hemorrhage - Bappaditya Ray; Vijay M. Pandav; Eleanor A. Mathews; David M. Thompson; Lance Ford; Lori K. Yearout; Bradley N. Bohnstedt; Shuchi Chaudhary; George L. Dale; Calin I. Prodan (Translational Stroke Research, 2018)

How accurate are satellite estimates of precipitation over the north Indian Ocean? - Satya Prakash; M. R. Ramesh Kumar; Simi Mathew; R. Venkatesan (Theoretical and Applied Climatology, 2018)

Assessing climatic trends of extreme rainfall indices over northeast Bangladesh - Md. Abul Basher; Mathew Alexander Stiller-Reeve; A. K. M. Saiful Islam; Scott Bremer (Theoretical and Applied Climatology, 2018)

Cenozoic conifer wood from the Gore Lignite Measures, Southland, New Zealand - Mathew R. Vanner; John G. Conran; Jennifer M. Bannister; Daphne E. Lee (New Zealand Journal of Botany, 2018)
Well preserved fossil wood in the form of tree stumps, logs, branches, roots and occasionally bark is common throughout the Gore Lignite Measures, southern New Zealand. The main objective of the present study is to identify the range of forest trees present using anatomical features such as: distinct growth rings; presence or absence of axial parenchyma; uniseriate to triseriate, opposite to alternate, separate or contiguous tracheid pitting; and taxodioid, cupressoid and araucarioid cross‐field pitting. Specimens of silicified and lignified wood are described and illustrated from four localities within the Late Oligocene–Early Miocene Gore Lignite Measures, Southland: Newvale Coal Mine; Mataura Coal Mine; Cosy Dell Coal Pit; and Bennett's Pit. The fossil wood specimens include examples of Araucariaceae, Cupressaceae and Podocarpaceae. Three specimens from Newvale Mine resemble Araucariaceae, while one is assigned to Cupressaceae. Cosy Dell Coal Pit preserved branches of Podocarpaceae . Large stumps and branches preserved at the Mataura Coal Mine are identified as Cupressaceae and Podocarpaceae . Wood recovered from Bennett's Pit resembles either Cupressaceae or Podocarpaceae. Araucariaceae, in the form of Agathis Salisb . trees are today restricted to the northern North Island. Cupressaceae and Podocarpaceae are still extant in modern forests throughout New Zealand. So far, no angiosperm wood has been recognised from the lignite deposits. The forests in which these trees lived were in or near oligotrophic swamps on a deltaic plain. Identification of samples of fossil wood provides new data that can be used to reconstruct the forest vegetation of the Gore Lignite Measures.

Evolutionary Divergence of TNL Disease-Resistant Proteins in Soybean (Glycine max) and Common Bean (Phaseolus vulgaris) - Surendra Neupane; Qin Ma; Febina M. Mathew; Adam J. Varenhorst; Ethan J. Andersen; Madhav P. Nepal (Biochemical Genetics, 2018)

Electro-Fenton oxidation of para-aminosalicylic acid: degradation kinetics and mineralization pathway using Pt/carbon-felt and BDD/carbon-felt cells - Nihal Oturan; Charuvila T. Aravindakumar; Hugo Olvera-Vargas; Mathew M. Sunil Paul; Mehmet A. Oturan (Environmental Science and Pollution Research, 2018)

Direct antifungal activity of tiadinil, a systemic acquired resistance inducer, and thymol formulations on Stagonosporopsis citrulli and control of watermelon gummy stem blight - Yonas Kefialew; Sanju Kunwar; Dawit Abate; Amare Ayalew; James Colee; Laura Ritchie; Stephen M. Olson; Mathews L. Paret (Journal of General Plant Pathology, 2018)

Aboveground Carbon Storage and Its Links to Stand Structure, Tree Diversity and Floristic Composition in South-Eastern Tanzania - Iain M. McNicol; Casey M. Ryan; Kyle G. Dexter; Stephen M. J. Ball; Mathew Williams (Ecosystems, 2018)

Morphology and surface ultrastructure of Dadaytrema oxycephala (Digenea: Cladorchiidae) with a new host record from Peruvian Amazon floodplain - Ruben C. Cuadros; Norma L. S. Rivadeneyra; José C. O. Malta; M. Enrique Serrano-Martínez; Patrick D. Mathews (Biologia, 2018)

Evaluation of radiative fluxes over the north Indian Ocean - M. R. Ramesh Kumar; Rachel T. Pinker; Simi Mathew; R. Venkatesan; W. Chen (Theoretical and Applied Climatology, 2018)

En masse lentiviral gene delivery to mouse fertilized eggs via laser perforation of zona pellucida - Negin P. Martin; Page Myers; Eugenia Goulding; Shih-Heng Chen; Mitzie Walker; Thomas M. Porter; Lucas Van Gorder; Amanda Mathew; Artiom Gruzdev; Charles Romeo (Transgenic Research, 2018)

Managing conflict between large carnivores and livestock - Lily M. van Eeden; Mathew S. Crowther; Chris R. Dickman; David W. Macdonald; William J. Ripple; Euan G. Ritchie; Thomas M. Newsome (Conservation Biology, 2018)
Large carnivores are persecuted globally because they threaten human industries and livelihoods. How this conflict is managed has consequences for the conservation of large carnivores and biodiversity more broadly. Mitigating human–predator conflict should be evidence‐based and accommodate people's values while protecting carnivores. Despite much research into human and large‐carnivore coexistence strategies, there have been few attempts to document the success of conflict‐mitigation strategies on a global scale. We conducted a meta‐analysis of global research on conflict mitigation related to large carnivores and humans. We focused on conflicts that arise from the threat large carnivores pose to livestock. We first used structured and unstructured searching to identify replicated studies that used before–after or control–impact design to measure change in livestock loss as a result of implementing a management intervention. We then extracted relevant data from these studies to calculate an overall effect size for each intervention type. Research effort and focus varied among continents and aligned with the histories and cultures that shaped livestock production and attitudes toward carnivores. Livestock guardian animals most effectively reduced livestock losses. Lethal control was the second most effective control, although its success varied the most, and guardian animals and lethal control did not differ significantly. Financial incentives have promoted tolerance of large carnivores in some settings and reduced retaliatory killings. We suggest coexistence strategies be location‐specific, incorporate cultural values and environmental conditions, and be designed such that return on financial investment can be evaluated. Improved monitoring of mitigation measures is urgently required to promote effective evidence‐based policy.

Emerging Technologies and Synergies for Airborne and Space-Based Measurements of Water Vapor Profiles - Amin R. Nehrir; Christoph Kiemle; Mathew D. Lebsock; Gottfried Kirchengast; Stefan A. Buehler; Ulrich Löhnert; Cong-Liang Liu; Peter C. Hargrave; Maria Barrera-Verdejo; David M. Winker (Surveys in Geophysics, 2017)
A deeper understanding of how clouds will respond to a warming climate is one of the outstanding challenges in climate science. Uncertainties in the response of clouds, and particularly shallow clouds, have been identified as the dominant source of the discrepancy in model estimates of equilibrium climate sensitivity. As the community gains a deeper understanding of the many processes involved, there is a growing appreciation of the critical role played by fluctuations in water vapor and the coupling of water vapor and atmospheric circulations. Reduction of uncertainties in cloud-climate feedbacks and convection initiation as well as improved understanding of processes governing these effects will result from profiling of water vapor in the lower troposphere with improved accuracy and vertical resolution compared to existing airborne and space-based measurements. This paper highlights new technologies and improved measurement approaches for measuring lower tropospheric water vapor and their expected added value to current observations. Those include differential absorption lidar and radar, microwave occultation between low-Earth orbiters, and hyperspectral microwave remote sensing. Each methodology is briefly explained, and measurement capabilities as well as the current technological readiness for aircraft and satellite implementation are specified. Potential synergies between the technologies are discussed, actual examples hereof are given, and future perspectives are explored. Based on technical maturity and the foreseen near-mid-term development path of the various discussed measurement approaches, we find that improved measurements of water vapor throughout the troposphere would greatly benefit from the combination of differential absorption lidar focusing on the lower troposphere with passive remote sensors constraining the upper-tropospheric humidity.

Environmental DNA metabarcoding: Transforming how we survey animal and plant communities - Kristy Deiner; Holly M. Bik; Elvira Mächler; Mathew Seymour; Anaïs Lacoursière‐Roussel; Florian Altermatt; Simon Creer; Iliana Bista; David M. Lodge; Natasha de Vere; Michael E. Pfrender; Louis Bernatchez (Molecular Ecology, 2017)
The genomic revolution has fundamentally changed how we survey biodiversity on earth. High‐throughput sequencing (“ HTS ”) platforms now enable the rapid sequencing of DNA from diverse kinds of environmental samples (termed “environmental DNA ” or “ eDNA ”). Coupling HTS with our ability to associate sequences from eDNA with a taxonomic name is called “ eDNA metabarcoding” and offers a powerful molecular tool capable of noninvasively surveying species richness from many ecosystems. Here, we review the use of eDNA metabarcoding for surveying animal and plant richness, and the challenges in using eDNA approaches to estimate relative abundance. We highlight eDNA applications in freshwater, marine and terrestrial environments, and in this broad context, we distill what is known about the ability of different eDNA sample types to approximate richness in space and across time. We provide guiding questions for study design and discuss the eDNA metabarcoding workflow with a focus on primers and library preparation methods. We additionally discuss important criteria for consideration of bioinformatic filtering of data sets, with recommendations for increasing transparency. Finally, looking to the future, we discuss emerging applications of eDNA metabarcoding in ecology, conservation, invasion biology, biomonitoring, and how eDNA metabarcoding can empower citizen science and biodiversity education.

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

High Ca2+ Influx During Traumatic Brain Injury Leads to Caspase-1-Dependent Neuroinflammation and Cell Death - P. M. Abdul Muneer; Mathew Long; Adriano Andrea Conte; Vijayalakshmi Santhakumar; Bryan J. Pfister (Molecular Neurobiology, 2017)

Development Considerations for Nanocrystal Drug Products - Mei-Ling Chen; Mathew John; Sau L. Lee; Katherine M. Tyner (The AAPS Journal, 2017)

Omega-3 Fatty Acid Protects Against Arsenic Trioxide-Induced Cardiotoxicity In Vitro and In Vivo - Mathews V. Varghese; M. Abhilash; M. V. Sauganth Paul; Manju Alex; R. Harikumaran Nair (Cardiovascular Toxicology, 2017)

Community assembly and the functioning of ecosystems: how metacommunity processes alter ecosystems attributes - Mathew A. Leibold; Jonathan M. Chase; S. K. Morgan Ernest (Ecology, 2017)
Recent work linking community structure and ecosystem function has primarily focused on the effects of local species richness but has neglected the dispersal‐dependent processes of community assembly that are ultimately involved in determining community structure and its relation to ecosystems. Here we combine simple consumer‐resource competition models and metacommunity theory with discussion of case studies to outline how spatial processes within metacommunities can alter community assembly and modify expectations about how species diversity and composition influence ecosystem attributes at local scales. We argue that when community assembly is strongly limited by dispersal, this can constrain ecosystem functioning by reducing positive selection effects (reducing the probability of the most productive species becoming dominant) even though it may often also enhance complementarity (favoring combinations of species that enhance production even though they may not individually be most productive). Conversely, excess dispersal with strong source‐sink relations among heterogeneous habitats can reduce ecosystem functioning by swamping local filters that would normally favor better‐suited species. Ecosystem function is thus most likely maximized at intermediate levels of dispersal where both of these effects are minimized. In this scenario, we find that the selection effect is maximized, while complementarity is often reduced and local diversity may often be relatively low. Our synthesis emphasizes that it is the entire set of community assembly processes that affect the functioning of ecosystems, not just the part that determines local species richness.

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Species Preference in Seedling Predation by the Sesarmid Crab Neosarmatium malabaricum (Henderson, 1893) in a Mangrove Forest in India - V. P. Praveen; K. Shanij; S. Suresh; Mathew M. Oommen; T. S. Nayar (Wetlands, 2017)

Contamination from organochlorine pesticides (OCPs) in agricultural soils of Kuttanad agroecosystem in India and related potential health risk - S. N. Sruthi; M. S. Shyleshchandran; Sunil Paul Mathew; E. V. Ramasamy (Environmental Science and Pollution Research, 2017)

Telemetry-Determined Habitat Use Informs Multi-Species Habitat Management in an Urban Harbour - Andrew M. Rous; Jonathon D. Midwood; Lee F.G. Gutowsky; Nicolas W.R. Lapointe; Rick Portiss; Thomas Sciscione; Mathew G. Wells; Susan E. Doka; Steven J. Cooke (Environmental Management, 2017)

Humpback whales interfering when mammal‐eating killer whales attack other species: Mobbing behavior and interspecific altruism? - Robert L. Pitman; Volker B. Deecke; Christine M. Gabriele; Mridula Srinivasan; Nancy Black; Judith Denkinger; John W. Durban; Elizabeth A. Mathews; Dena R. Matkin; Janet L. Neilson; Alisa Schulman‐Janiger; Debra Shearwater; et al. (Marine Mammal Science, 2017)
Humpback whales ( Megaptera novaeangliae ) are known to interfere with attacking killer whales ( Orcinus orca ). To investigate why, we reviewed accounts of 115 interactions between them. Humpbacks initiated the majority of interactions (57% vs . 43%; n = 72), although the killer whales were almost exclusively mammal‐eating forms ( MEKW s, 95%) vs . fish‐eaters (5%; n = 108). When MEKW s approached humpbacks ( n = 27), they attacked 85% of the time and targeted only calves. When humpbacks approached killer whales ( n = 41), 93% were MEKW s, and ≥87% of them were attacking or feeding on prey at the time. When humpbacks interacted with attacking MEKW s, 11% of the prey were humpbacks and 89% comprised 10 other species, including three cetaceans, six pinnipeds, and one teleost fish. Approaching humpbacks often harassed attacking MEKW s (≥55% of 56 interactions), regardless of the prey species, which we argue was mobbing behavior. Humpback mobbing sometimes allowed MEKW prey, including nonhumpbacks, to escape. We suggest that humpbacks initially responded to vocalizations of attacking MEKW s without knowing the prey species targeted. Although reciprocity or kin selection might explain communal defense of conspecific calves, there was no apparent benefit to humpbacks continuing to interfere when other species were being attacked. Interspecific altruism, even if unintentional, could not be ruled out.

Temperature‐driven changes in the diet preference of omnivorous copepods: no more meat when it's hot? A response to Winder et al . - Maarten Boersma; K. Avarachen Mathew; Barbara Niehoff; Katherina L. Schoo; Rita M. Franco‐Santos; Cédric L. Meunier (Ecology Letters, 2016)
The study of environmental impact on feeding preferences of omnivores is a rapidly growing field. Here, we show that the criticism put forward in a comment on our original study is largely unfounded.

Development of Web Based Road Accident Data Management System in GIS Environment: a Case Study - Ashish Dhamaniya; Mathew Sonu; M. Krishnanunni; Pynam Praveen; Austin Jaijin (Journal of the Indian Society of Remote Sensing, 2016)

Chemical profile, antiproliferative and antioxidant activities of rhizome oil of Zingiber anamalayanum from Western Ghats in India - Mohamed Salim; T.K. Ahmedul Kabeer; S. Ajikumaran Nair; Mathew Dan; M. Sabu; Sabulal Baby (Natural Product Research, 2016)

Relating fish health and reproductive metrics to contaminant bioaccumulation at the Tennessee Valley Authority Kingston coal ash spill site - Brenda M. Pracheil; S. Marshall Adams; Mark S. Bevelhimer; Allison M. Fortner; Mark S. Greeley; Cheryl A. Murphy; Teresa J. Mathews; Mark J. Peterson (Ecotoxicology, 2016)

Electronic cigarette inhalation alters innate immunity and airway cytokines while increasing the virulence of colonizing bacteria - John H. Hwang; Matthew Lyes; Katherine Sladewski; Shymaa Enany; Elisa McEachern; Denzil P. Mathew; Soumita Das; Alexander Moshensky; Sagar Bapat; David T. Pride; Weg M. Ongkeko; Laura E. Crotty Alexander (Journal of Molecular Medicine, 2016)

Intravesical PAC1 Receptor Antagonist, PACAP(6–38), Reduces Urinary Bladder Frequency and Pelvic Sensitivity in NGF-OE Mice - Beatrice M. Girard; Susan E. Malley; Morgan M. Mathews; Victor May; Margaret A. Vizzard (Journal of Molecular Neuroscience, 2016)

Taxonomy of prokaryotic viruses: update from the ICTV bacterial and archaeal viruses subcommittee - Mart Krupovic; Bas E. Dutilh; Evelien M. Adriaenssens; Johannes Wittmann; Finn K. Vogensen; Mathew B. Sullivan; Janis Rumnieks; David Prangishvili; Rob Lavigne; Andrew M. Kropinski; Jochen Klumpp; Annika Gillis; et al. (Archives of Virology, 2016)

A randomized, placebo-controlled pilot trial of the delta opioid receptor agonist AZD2327 in anxious depression - Erica M. Richards; Daniel C. Mathews; David A. Luckenbaugh; Dawn F. Ionescu; Rodrigo Machado-Vieira; Mark J. Niciu; Wallace C. Duncan; Neal M. Nolan; Jose A. Franco-Chaves; Thomas Hudzik; Carla Maciag; Shuang Li; et al. (Psychopharmacology, 2016)

Dissipation kinetics and effect of processing on imidacloprid and its metabolites in cardamom (Elettaria cardamomum Maton) - N. Pratheeshkumar; M. Chandran; S. Naseema Beevi; Thomas Biju Mathew; Thomas George; Ambily Paul; George Xavier; K. Prathibha Ravi; S. Visal Kumar; R. Rajith (Environmental Monitoring and Assessment, 2016)

Intensification of Southern Hemisphere westerly winds 2000–1000 years ago: evidence from the subantarctic Campbell and Auckland Islands (52–50°S) - Chris S. M. Turney; Matt M c Glone; Jonathan Palmer; Christopher Fogwill; Alan Hogg; Zoë A. Thomas; Mathew Lipson; Janet M. Wilmshurst; Pavla Fenwick; Richard T. Jones; Ben Hines; Graeme F. Clark (Journal of Quaternary Science, 2016)
The Southern Ocean plays a significant role in driving global climate–ocean–carbon dynamics. Unfortunately, a relative dearth of datasets across the region limits our ability to understand past and future mechanisms of change. Here we report a new dataset from the south‐west Pacific: radiocarbon‐dated subfossil tree stumps ( Dracophyllum ) eroding out from peat exposures on Campbell and Auckland Islands (52–50°S). Dracophyllum are the southernmost growing trees in the south‐west Pacific and their growth on exposed sites and at altitude is strongly controlled by the prevailing westerly airflow, providing a unique measure of past changes in zonal wind strength. Here we demonstrate a significant collapse in the altitudinal limit of growth between approximately 2000 and 1000 years ago (hereafter 2–1 ka), consistent with other records across the Southern Hemisphere that indicate westerly airflow was significantly enhanced. Importantly, this period in the late Holocene was one of marked change across the broader region, suggesting westerly airflow played a key role in driving Southern Ocean variability at this time.

Temperature driven changes in the diet preference of omnivorous copepods: no more meat when it's hot? - Maarten Boersma; K. Avarachen Mathew; Barbara Niehoff; Katherina L. Schoo; Rita M. Franco‐Santos; Cédric L. Meunier (Ecology Letters, 2016)
Herbivory is more prevalent in the tropics than at higher latitudes. If differences in ambient temperature are the direct cause for this phenomenon, then the same pattern should be visible in a seasonal gradient, as well as in experiments manipulating temperature. Using 15 N stable isotope analyses of natural populations of the copepod Temora longicornis we indeed observed seasonal differences in the trophic level of the copepod and a decrease in trophic level with increasing temperature. In a grazing experiment, with a mixed diet of the cryptophyte Rhodomonas salina and the heterotrophic dinoflagellate Oxyrrhis marina, T. longicornis preferred the cryptophyte at higher temperatures, whereas at lower temperatures it preferred the non‐autotrophic prey. We explain these results by the higher relative carbon content of primary producers compared to consumers, in combination with the higher demand for metabolic carbon at higher temperatures. Thus, currently increasing temperatures may cause changes in dietary preferences of many consumers.

Identification and characterization of Fusarium spp. associated with root rots of field pea in North Dakota - Kishore Chittem; Febina M. Mathew; Matthew Gregoire; Robin S. Lamppa; Yen Wei Chang; Samuel G. Markell; Carl A. Bradley; Tharcisse Barasubiye; Rubella S. Goswami (European Journal of Plant Pathology, 2015)

First record of coralline lethal orange disease (CLOD) in the Indian Ocean - G. S. Aeby; K. Diraviya Raj; G. Mathews; M. Selva Bharath; J. K. Patterson Edward (Coral Reefs, 2015)

Short-horned grasshopper subfamilies feed at different rates on big bluestem and switchgrass cultivars - Muhammad Irfan Ullah; Fatima Mustafa; William W. Hoback; Mathew L. Brust; Kerri M. Farnsworth-Hoback; John E. Foster (Biologia, 2015)

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

Multi-target drugs to address multiple checkpoints in complex inflammatory pathologies: evolutionary cues for novel “first-in-class” anti-inflammatory drug candidates: a reviewer’s perspective - Geetha Mathew; M. K. Unnikrishnan (Inflammation Research, 2015)

Negative mood reverses devaluation of goal-directed drug-seeking favouring an incentive learning account of drug dependence - Lee Hogarth; Zhimin He; Henry W. Chase; Andy J. Wills; Joseph Troisi; Adam M. Leventhal; Amanda R. Mathew; Brian Hitsman (Psychopharmacology, 2015)

Diel bank migration of Burbot (Lota lota) - Peter A. Cott; Mathew M. Guzzo; A. J. Chapelsky; Scott W. Milne; Paul J. Blanchfield (Hydrobiologia, 2015)

A rapid PCR-based test for identification of fifteen British bat species - P. B. Hamilton; T. M. Uren Webster; M. Basiewicz; E. V. Kennedy; E. S. R. De-Bastos; F. Mathews (Conservation Genetics Resources, 2015)

Observational evidence of Mixed Rossby Gravity waves at the central equatorial Indian Ocean - P. M. Muraleedharan; S. Prasanna Kumar; K. Mohana kumar; S. Sijikumar; K. U. Sivakumar; Teesha Mathew (Meteorology and Atmospheric Physics, 2015)

Linking place-based science to people through spatial narratives of coastal stewardship - J. Silbernagel; G. Host; C. Hagley; D. Hart; R. Axler; R. Fortner; M. Axler; V. Smith; A. Drewes; W. Bartsch; N. Danz; J. Mathews; et al. (Journal of Coastal Conservation, 2015)

mGluR5 positive allosteric modulation and its effects on MK-801 induced set-shifting impairments in a rat operant delayed matching/non-matching-to-sample task - Amber L. LaCrosse; Brian T. Burrows; Rachel M. Angulo; Phoebe R. Conrad; Sarah M. Himes; Nordia Mathews; Scott A. Wegner; Sara B. Taylor; M. Foster Olive (Psychopharmacology, 2015)

Molecular characterization of Xanthomonas strains responsible for bacterial spot of tomato in Ethiopia - Misrak Kebede; Sujan Timilsina; Amare Ayalew; Belayneh Admassu; Neha Potnis; Gerald V. Minsavage; Erica M. Goss; Jason C. Hong; Amanda Strayer; Mathews Paret; Jeffrey B. Jones; Gary E. Vallad (European Journal of Plant Pathology, 2014)

Life history traits, but not phylogeny, drive compositional patterns in a butterfly metacommunity - Sandrine Pavoine; Michel Baguette; Virginie M. Stevens; Mathew A. Leibold; Camille Turlure; Michael B. Bonsall (Ecology, 2014)
Community assembly is a combination of ecological, evolutionary, and stochastic processes. Separating out the abiotic and biotic processes (such as limiting similarity or environmental filtering) from stochastic processes is central to developing a cogent approach for understanding patterns in ecological community structure and organization. Using butterfly communities in a fragmented landscape, we tested the hypothesis that local environmental filtering drives character convergences in traits of species belonging to different clades. We found that, while many traits were determined both by phylogeny and environment, trait convergence within the phylogeny was extensive and eroded the phylogenetic structure associated with habitat use. Traits associated with habitat use are shown to be only moderately phylogenetically conserved in chalk grassland butterfly assemblages, and further analysis revealed that traits associated with environmental filtering may be highly labile rather than phylogenetically conserved. In general, a significant phylogenetic signal is therefore neither sufficient to demonstrate a lack of trait convergence, nor to determine whether communities are likely to be phylogenetically structured. We conclude that explicit trait‐based approaches should be used in preference to the more indirect approach based on phylogenetic conservatism for understanding metacommunity assembly processes.

Rapid recolonisation by the European red fox: how effective are uncoordinated and isolated control programs? - Thomas M. Newsome; Mathew S. Crowther; Christopher R. Dickman (European Journal of Wildlife Research, 2014)

Whole-genome analyses of DS-1-like human G2P[4] and G8P[4] rotavirus strains from Eastern, Western and Southern Africa - Martin M. Nyaga; Karla M. Stucker; Mathew D. Esona; Khuzwayo C. Jere; Bakari Mwinyi; Annie Shonhai; Enyonam Tsolenyanu; Augustine Mulindwa; Julia N. Chibumbya; Hokororo Adolfine; Rebecca A. Halpin; Sunando Roy; et al. (Virus Genes, 2014)

Persistence and effect of processing on reduction of fipronil and its metabolites in chilli pepper (Capsicum annum L.) fruits - George Xavier; M. Chandran; Thomas George; S. Naseema Beevi; Thomas Biju Mathew; Ambily Paul; Ranjith Arimboor; V. Vijayasree; G. T. Pradeepkumar; R. Rajith (Environmental Monitoring and Assessment, 2014)

Measured and Back Analysed Soil Structure Interaction Effects in a Layered Stratigraphy During Tunnel Boring - Gima V. Mathew; Barry M. Lehane (Geotechnical and Geological Engineering, 2014)

Performance evaluation of environmentally compatible stormwater filtration systems - M. P. Samuel; S. Senthilvel; A. C. Mathew (International Journal of Environmental Science and Technology, 2014)

Population pharmacokinetics of intravenous acetaminophen and its metabolites in major surgical patients - Katie H. Owens; Philip G. M. Murphy; Natalie J. Medlicott; Julia Kennedy; Mathew Zacharias; Neil Curran; Sree Sreebhavan; Mark Thompson-Fawcett; David M. Reith (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Assessing the enrichment of heavy metals in surface soil and plant (Digitaria eriantha) around coal-fired power plants in South Africa - Olumuyiwa O. Okedeyi; Simiso Dube; Omotayo R. Awofolu; Mathew M. Nindi (Environmental Science and Pollution Research, 2014)

Neurocognitive effects of ketamine in treatment-resistant major depression: association with antidepressant response - James W. Murrough; Le-Ben Wan; Brian Iacoviello; Katherine A. Collins; Carly Solon; Benjamin Glicksberg; Andrew M. Perez; Sanjay J. Mathew; Dennis S. Charney; Dan V. Iosifescu; Katherine E. Burdick (Psychopharmacology, 2014)

Sub-hourly changes in biogeochemical properties in surface waters of Zuari estuary, Goa - S. Subha Anand; K. J. Anju; Dayana Mathew; M. Dileep Kumar (Environmental Monitoring and Assessment, 2014)

Testing the sensitivity of the East Antarctic Ice Sheet to Southern Ocean dynamics: past changes and future implications - CHRISTOPHER J. FOGWILL; CHRISTIAN S. M. TURNEY; KATRIN J. MEISSNER; NICHOLAS R. GOLLEDGE; PAUL SPENCE; JASON L. ROBERTS; MATHEW H. ENGLAND; RICHARD T. JONES; LIONEL CARTER (Journal of Quaternary Science, 2014)
The stability of Antarctic ice sheets and their potential contribution to sea level under projected future warming remains highly uncertain. The Last Interglacial (135 000–116 000 years ago) provides a potential analogue, with global temperatures 2 °C higher and rates of sea‐level rise >5.6 m ka −1 , leading to sea levels 6.6–9.4 m higher than present. The source(s) of this sea‐level rise remain fiercely debated. Here we report a series of independent model simulations exploring the effects of migrating Southern Hemisphere Westerlies (SHWs) on Southern Ocean circulation and Antarctic ice‐sheet dynamics. We suggest that southerly shifts in winds may have significantly impacted the sub‐polar gyres, inducing pervasive warming (0.2–0.8 °C in the upper 1200 m) adjacent to sectors of the East Antarctic Ice Sheet (EAIS), which due to their geometries and connectivity to the Southern Ocean are highly sensitive to ocean forcing. We conclude that the EAIS potentially made a substantial, hitherto unsuspected, contribution to interglacial sea levels, and given 21st‐century projections in the Southern Annular Mode and associated SHW migration, we highlight how pervasive circum‐Antarctic warming may threaten EAIS stability.

Genetic Diversity in Exon 2 of the Major Histocompatibility Complex Class II DQB1 Locus in Nigerian Goats - Abdulmojeed Yakubu; Adebowale E. Salako; Marcos De Donato; Michael I. Takeet; Sunday O. Peters; Mufliat A. Adefenwa; Moses Okpeku; Mathew Wheto; Brilliant O. Agaviezor; Timothy M. Sanni; Oyeyemi O. Ajayi; Gbolabo O. Onasanya; et al. (Biochemical Genetics, 2013)

A novel rearrangement of occludin causes brain calcification and renal dysfunction - Marissa A. LeBlanc; Lynette S. Penney; Daniel Gaston; Yuhao Shi; Erika Aberg; Mathew Nightingale; Haiyan Jiang; Roxanne M. Gillett; Somayyeh Fahiminiya; Christine Macgillivray; Ellen P. Wood; Philip D. Acott; et al. (Human Genetics, 2013)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Mitochondrial VDAC and hexokinase together modulate plant programmed cell death - Ashwini Godbole; Ashvini Kumar Dubey; Palakolanu S. Reddy; M. Udayakumar; Mathew K. Mathew (Protoplasma, 2013)

Erratum to: QTL for yield and associated traits in the Seri/Babax population grown across several environments in Mexico, in the West Asia, North Africa, and South Asia regions - Marta S. Lopes; Matthew P. Reynolds; C. Lynne McIntyre; Ky L. Mathews; M. R. Jalal Kamali; Moussa Mossad; Yousef Feltaous; Izzat S. A. Tahir; Ravish Chatrath; Francis Ogbonnaya; Michael Baum (Theoretical and Applied Genetics, 2013)

QTL for yield and associated traits in the Seri/Babax population grown across several environments in Mexico, in the West Asia, North Africa, and South Asia regions - Marta S. Lopes; Matthew P. Reynolds; C. Lynne McIntyre; Ky L. Mathews; M. R. Jalal Kamali; Moussa Mossad; Yousef Feltaous; Izzat S. A. Tahir; Ravish Chatrath; Francis Ogbonnaya; Michael Baum (Theoretical and Applied Genetics, 2013)

Distribution and potential sources of polycyclic aromatic hydrocarbons in soils around coal-fired power plants in South Africa - Olumuyiwa O. Okedeyi; Mathew M. Nindi; Simiso Dube; O. R. Awofolu (Environmental Monitoring and Assessment, 2013)

PM2.5 in the central part of Upper Silesia, Poland: concentrations, elemental composition, and mobility of components - W. Rogula-Kozłowska; B. Błaszczak; S. Szopa; K. Klejnowski; I. Sówka; A. Zwoździak; M. Jabłońska; B. Mathews (Environmental Monitoring and Assessment, 2013)

UV-Visible Photoluminescence of TiO2 Nanoparticles Prepared by Hydrothermal Method - S. Mathew; Amit kumar Prasad; Thomas Benoy; P. P. Rakesh; Misha Hari; T. M Libish; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2012)

Kuroshio pathways in a climatologically forced model - Elizabeth M. Douglass; Steven R. Jayne; Frank O. Bryan; Synte Peacock; Mathew Maltrud (Journal of Oceanography, 2012)

Carbon Stocks in an African Woodland Landscape: Spatial Distributions and Scales of Variation - Emily Woollen; Casey M. Ryan; Mathew Williams (Ecosystems, 2012)

Complete genome sequencing and evolutionary analysis of dengue virus serotype 1 isolates from an outbreak in Kerala, South India - M. Anoop; Ashish J. Mathew; B. Jayakumar; Aneesh Issac; Sajith Nair; Rachy Abraham; M. G. Anupriya; E. Sreekumar (Virus Genes, 2012)

Analysis of doramectin in the serum of repeatedly treated pastured cattle used to predict the probability of cattle fever ticks (Acari: Ixodidae) feeding to repletion - Ronald B. Davey; J. Mathews Pound; Jerome A. Klavons; Kimberly H. Lohmeyer; Jeanne M. Freeman; Pia U. Olafson (Experimental and Applied Acarology, 2012)

Influence of accurate and inaccurate ‘split-time’ feedback upon 10-mile time trial cycling performance - Mathew G. Wilson; Andy M. Lane; Chris J. Beedie; Abdulaziz Farooq (European Journal of Applied Physiology, 2012)

Quantifying small‐scale deforestation and forest degradation in African woodlands using radar imagery - Casey M. Ryan; Timothy Hill; Emily Woollen; Claire Ghee; Edward Mitchard; Gemma Cassells; John Grace; Iain H. Woodhouse; Mathew Williams (Global Change Biology, 2012)
Carbon emissions from tropical land‐use change are a major uncertainty in the global carbon cycle. In African woodlands, small‐scale farming and the need for fuel are thought to be reducing vegetation carbon stocks, but quantification of these processes is hindered by the limitations of optical remote sensing and a lack of ground data. Here, we present a method for mapping vegetation carbon stocks and their changes over a 3‐year period in a > 1000 km 2 region in central Mozambique at 0.06 ha resolution. L‐band synthetic aperture radar imagery and an inventory of 96 plots are combined using regression and bootstrapping to generate biomass maps with known uncertainties. The resultant maps have sufficient accuracy to be capable of detecting changes in forest carbon stocks of as little as 12 MgC ha −1 over 3 years with 95% confidence. This allows characterization of biomass loss from deforestation and forest degradation at a new level of detail. Total aboveground biomass in the study area was reduced by 6.9 ± 4.6% over 3 years: from 2.13 ± 0.12 TgC in 2007 to 1.98 ± 0.11 TgC in 2010, a loss of 0.15 ± 0.10 TgC. Degradation probably contributed 67% (96.9 ± 91.0 GgC) of the net loss of biomass, but is associated with high uncertainty. The detailed mapping of carbon stock changes quantifies the nature of small‐scale farming. New clearances were on average small (median 0.2 ha) and were often additions to already cleared land. Deforestation events reduced biomass from 33.5 to 11.9 MgC ha −1 on average . Contrary to expectations, we did not find evidence that clearances were targeted towards areas of high biomass. Our method is scalable and suitable for monitoring land cover change and vegetation carbon stocks in woodland ecosystems, and can support policy approaches towards reducing emissions from deforestation and degradation ( REDD ).

Genomewide linkage analysis in Costa Rican families implicates chromosome 15q14 as a candidate region for OCD - Jessica Ross; Judith Badner; Helena Garrido; Brooke Sheppard; Denise A. Chavira; Marco Grados; Jonathan M. Woo; Pamela Doo; Paula Umaña; Eduardo Fournier; Sarah Shaw Murray; Carol A. Mathews (Human Genetics, 2011)

Characterization of cucumber vein-clearing virus, a whitefly (Bemisia tabaci G.)-transmitted carlavirus - Wulf Menzel; Mathew M. Abang; Stephan Winter (Archives of Virology, 2011)

Bacterial Expression, Purification and Characterization of a Rice Voltage-Dependent, Anion-Selective Channel Isoform, OsVDAC4 - Ashwini Godbole; Rohan Mitra; Ashvini K. Dubey; Palakolanu S. Reddy; M. K. Mathew (The Journal of Membrane Biology, 2011)

Population growth and colonization of Steller sea lions in the Glacier Bay region of southeastern Alaska: 1970s–2009 - Elizabeth A. Mathews; Jamie N. Womble; Grey W. Pendleton; Lauri A. Jemison; John M. Maniscalco; Greg Streveler (Marine Mammal Science, 2011)
We estimated trends in numbers of Steller sea lions in the Glacier Bay region of the eastern population from the 1970s to 2009. We documented the colonization of several new haul‐outs and the transition of one haul‐out (Graves Rocks) to a rookery, assessed seasonal patterns in distribution, and compared counts from different observation platforms. Sea lions increased in the region by 8.2%/yr (95%CI = 6.4%–10.0%), with the most growth at South Marble Island in Glacier Bay (16.6%/yr, 1991–2009) and rapid growth in Cross Sound. Seasonal patterns in the distribution of sea lions were likely influenced by new breeding opportunities and the seasonal availability of prey. Factors that likely contributed to the exceptional growth include availability of new habitat following deglaciation, immigration, redistribution, decreases in mortality, and ecosystem‐level changes. The rapid increase in sea lion numbers in this region is of particular interest in light of dramatic declines in the western population and evidence that Steller sea lions from both the eastern and western populations colonized the Graves Rocks rookery. The colonization and rookery development in this dynamic area may signal the reversal of the reproductive isolation of the two populations.

Is productivity of mesic savannas light limited or water limited? Results of a simulation study - RHYS J. WHITLEY; CATRIONA M. O. MACINNIS‐NG; LINDSAY B. HUTLEY; JASON BERINGER; MELANIE ZEPPEL; MATHEW WILLIAMS; DANIEL TAYLOR; DEREK EAMUS (Global Change Biology, 2011)
A soil–plant–atmosphere model was used to estimate gross primary productivity (GPP) and evapotranspiration (ET) of a tropical savanna in Australia. This paper describes model modifications required to simulate the substantial C4 grass understory together with C3 trees. The model was further improved to include a seasonal distribution of leaf area and foliar nitrogen through 10 canopy layers. Model outputs were compared with a 5‐year eddy covariance dataset. Adding the C4 photosynthesis component improved the model efficiency and root‐mean‐squared error (RMSE) for total ecosystem GPP by better emulating annual peaks and troughs in GPP across wet and dry seasons. The C4 photosynthesis component had minimal impact on modelled values of ET. Outputs of GPP from the modified model agreed well with measured values, explaining between 79% and 90% of the variance and having a low RMSE (0.003–0.281 g C m −2 day −1 ). Approximately, 40% of total annual GPP was contributed by C4 grasses. Total (trees and grasses) wet season GPP was approximately 75–80% of total annual GPP. Light‐use efficiency (LUE) was largest for the wet season and smallest in the dry season and C4 LUE was larger than that of the trees. A sensitivity analysis of GPP revealed that daily GPP was most sensitive to changes in leaf area index (LAI) and foliar nitrogen (N f ) and relatively insensitive to changes in maximum carboxylation rate ( V cmax ), maximum electron transport rate ( J max ) and minimum leaf water potential ( ψ min ). The modified model was also able to represent daily and seasonal patterns in ET, (explaining 68–81% of variance) with a low RMSE (0.038–0.19 mm day −1 ). Current values of N f , LAI and other parameters appear to be colimiting for maximizing GPP. By manipulating LAI and soil moisture content inputs, we show that modelled GPP is limited by light interception rather than water availability at this site.

Uniformity of rotavirus strain nomenclature proposed by the Rotavirus Classification Working Group (RCWG) - Jelle Matthijnssens; Max Ciarlet; Sarah M. McDonald; Houssam Attoui; Krisztián Bányai; J. Rodney Brister; Javier Buesa; Mathew D. Esona; Mary K. Estes; Jon R. Gentsch; Miren Iturriza-Gómara; Reimar Johne; et al. (Archives of Virology, 2011)

DNA repair: the culprit for tumor-initiating cell survival? - Lesley A. Mathews; Stephanie M. Cabarcas; William L. Farrar (Cancer and Metastasis Reviews, 2011)

Long-Term Variability of Nutrients and Chlorophyll in the Chesapeake Bay: A Retrospective Analysis, 1985–2008 - M. Bala Krishna Prasad; Mathew R. P. Sapiano; Clarissa R. Anderson; Wen Long; Raghu Murtugudde (Estuaries and Coasts, 2010)

Survey of a Salivary Effector in Caterpillars: Glucose Oxidase Variation and Correlation with Host Range - Herb Eichenseer; M. C. Mathews; Jaimie S. Powell; Gary W. Felton (Journal of Chemical Ecology, 2010)

Evolution, Homology Conservation, and Identification of Unique Sequence Signatures in GH19 Family Chitinases - N. A. Udaya Prakash; M. Jayanthi; R. Sabarinathan; P. Kangueane; Lazar Mathew; K. Sekar (Journal of Molecular Evolution, 2010)

Genetic characterization of 2006–2008 isolates of Chikungunya virus from Kerala, South India, by whole genome sequence analysis - E. Sreekumar; Aneesh Issac; Sajith Nair; Ramkumar Hariharan; M. B. Janki; D. S. Arathy; R. Regu; Thomas Mathew; M. Anoop; K. P. Niyas; M. R. Pillai (Virus Genes, 2010)

Erratum to: Molecular characterization of a rare, human-porcine reassortant rotavirus strain, G11P[6], from Ecuador - Krisztián Bányai; Mathew D. Esona; Tara K. Kerin; Jennifer J. Hull; Slavica Mijatovic; Nancy Vásconez; Carlos Torres; Ana M. B. de Filippis; Kimberly R. Foytich; Jon R. Gentsch (Archives of Virology, 2010)

Harbor seal ( Phoca vitulina richardii ) decline continues in the rapidly changing landscape of Glacier Bay National Park, Alaska 1992-2008 - Jamie N. Womble; Grey W. Pendleton; Elizabeth A. Mathews; Gail M. Blundell; Natalie M. Bool; Scott M. Gende (Marine Mammal Science, 2009)

Molecular characterization of a rare, human-porcine reassortant rotavirus strain, G11P[6], from Ecuador - Krisztián Bányai; Mathew D. Esona; Tara K. Kerin; Jennifer J. Hull; Slavica Mijatovic; Nancy Vásconez; Carlos Torres; Ana M. B. de Filippis; Jon R. Gentsch (Archives of Virology, 2009)

MET Y1253D-activating point mutation and development of distant metastasis in advanced head and neck cancers - Pirus Ghadjar; Wieslawa Blank-Liss; Mathew Simcock; Ivan Hegyi; Karl T. Beer; Holger Moch; Daniel M. Aebersold; Yitzhak Zimmer (Clinical & Experimental Metastasis, 2009)

Post-harvest deterioration of sugarcane with special reference to quality loss - P. Rakkiyappan; D. Esther Shekinah; P. Gopalasundaram; M. D. Mathew; S. Asokan (Sugar Tech, 2009)

The role of root apoplastic transport barriers in salt tolerance of rice (Oryza sativa L.) - Pannaga Krishnamurthy; Kosala Ranathunge; Rochus Franke; H. S. Prakash; Lukas Schreiber; M. K. Mathew (Planta, 2009)

Invasive prostate cancer cells are tumor initiating cells that have a stem cell-like genomic signature - George J. Klarmann; Elaine M. Hurt; Lesley A. Mathews; Xiaohu Zhang; Maria A. Duhagon; Tashan Mistree; Suneetha B. Thomas; William L. Farrar (Clinical & Experimental Metastasis, 2009)

Short Term Exposure to a Violent Video Game Induces Changes in Frontolimbic Circuitry in Adolescents - Yang Wang; Vincent P. Mathews; Andrew J. Kalnin; Kristine M. Mosier; David W. Dunn; Andrew J. Saykin; William G. Kronenberger (Brain Imaging and Behavior, 2009)

ENVIRONMENTAL FLUCTUATIONS INDUCE SCALE‐DEPENDENT COMPENSATION AND INCREASE STABILITY IN PLANKTON ECOSYSTEMS - Amy L. Downing; Bryan L. Brown; Elizabeth M. Perrin; Timothy H. Keitt; Mathew A. Leibold (Ecology, 2008)
The temporal stability of aggregate community and ecosystem properties is influenced by the variability of component populations, the interactions among populations, and the influence of environmental fluctuations on populations. Environmental fluctuations that enhance population variability are generally expected to destabilize community and ecosystem properties, but this will depend on the degree to which populations are synchronized in their dynamics. Here we use seminatural experimental ponds to show that reduced synchrony among zooplankton taxa increases the temporal stability of zooplankton density, abundance, and ecosystem productivity in fluctuating environments. However, asynchrony only occurs at long timescales (∼80‐day periods) and under recurring environmental perturbations. At shorter timescales (∼10‐day periods) and in constant environments, synchronous dynamics dominate. Our findings support recent theory indicating that compensatory dynamics can stabilize communities and ecosystems. They further indicate that environmental fluctuations can enhance the likelihood of long‐period asynchrony and thus stabilize community and ecosystem properties despite their short term destabilizing effects.

Population Structure and Diversity in Finger Millet (Eleusine coracana) Germplasm - Mathews M. Dida; Nelson Wanyera; Melanie L. Harrison Dunn; Jeffrey L. Bennetzen; Katrien M. Devos (Tropical Plant Biology, 2008)

Distance Communication of Sexual Status in the Crayfish Orconectes quinebaugensis: Female Sexual History Mediates Male and Female Behavior - William S. Durgin; Kelly E. Martin; Heather R. Watkins; Lauren M. Mathews (Journal of Chemical Ecology, 2008)

Simulated glacial and interglacial vegetation across Africa: implications for species phylogenies and trans‐African migration of plants and animals - SHARON A. COWLING; PETER M. COX; CHRIS D. JONES; MARK A. MASLIN; MATHEW PEROS; STEVEN A. SPALL (Global Change Biology, 2008)
The paleoenvironmental context of plant and animal species evolution (including glacial migrations and population separations) is based on a very patchy and incomplete paleo‐phytogeographic record. It was our objective, therefore, to provide an additional source for paleovegetation comparison by presenting simulations from a state‐of‐the‐art fully coupled earth system model (HadCM3LC). We simulated potential paleovegetation distributions following pre‐Industrial and last glacial maximum (LGM) climate forcing for the continent of Africa. Our LGM simulations indicate that tropical broadleaf forest was not severely displaced by expanding grasslands within central Africa, although the outer extent of closed forest decreases, particularly in the north. Our simulations indicate that the structure of glacial forests may have been much different from today, in that LGM simulations indicate that forests were likely characterized by lower leaf area indexes, lower tree heights and lower vegetation carbon content. On the other hand, warmer interglacial climate (like our pre‐Industrial climate scenario) results in simulated expansion of tropical forest from coast to coast across central Africa that we postulate could have acted as a barrier to plant and animal species migrations. We suggest that our modeling experiments have implications for the interpretation of phylogenetic data, including that of our own species, Homo sapiens sapiens .

Species of natural hybrid origin and misinformation in the Irises: A reappraisal of the presence of I. aphylla L. in Italy - M. Colasante; B. Mathew (Plant Biosystems, 2008)

Limestone Neutralisation of Arsenic-Rich Effluent from a Gold Mine - M. de Beer; E. H. Mathews; D. Krueger; J. Maree; N. Mbhele; M. Phalanndwa; O. Novhe (Mine Water and the Environment, 2008)

Characterization of a SEPT9 interacting protein, SEPT14, a novel testis-specific septin - Esther A. Peterson; Linda M. Kalikin; Jonathan D. Steels; Mathew P. Estey; William S. Trimble; Elizabeth M. Petty (Mammalian Genome, 2007)

Relationships between height and yield in near-isogenic spring wheats that contrast for major reduced height genes - S. C. Chapman; K. L. Mathews; R. M. Trethowan; R. P. Singh (Euphytica, 2007)

Evidence for restricted gene flow over small spatial scales in a marine snapping shrimp Alpheus angulosus - Lauren M. Mathews (Marine Biology, 2007)

Comparative analyses reveal high levels of conserved colinearity between the finger millet and rice genomes - Srinivasachary; Mathews M. Dida; Mike D. Gale; Katrien M. Devos (Theoretical and Applied Genetics, 2007)

Beneficial effects of ketogenic diet in obese diabetic subjects - Hussein M. Dashti; Thazhumpal C. Mathew; Mousa Khadada; Mahdi Al-Mousawi; Husain Talib; Sami K. Asfar; Abdulla I. Behbahani; Naji S. Al-Zaid (Molecular and Cellular Biochemistry, 2007)

Genetic diversity of Rhynchosporium secalis in Tunisia as revealed by pathotype, AFLP, and microsatellite analyses - Aida Bouajila; Mathew M. Abang; Samira Haouas; Sripada Udupa; Salah Rezgui; Michael Baum; Amor Yahyaoui (Mycopathologia, 2007)

The genetic map of finger millet, Eleusine coracana - Mathews M. Dida; Srinivasachary; Sujatha Ramakrishnan; Jeffrey L. Bennetzen; Mike D. Gale; Katrien M. Devos (Theoretical and Applied Genetics, 2006)

Cryptic biodiversity and phylogeographical patterns in a snapping shrimp species complex - LAUREN M. MATHEWS (Molecular Ecology, 2006)
Recent investigations suggest that marine biodiversity may be much higher than earlier estimates, and an important hidden source of diversity in marine systems is the phenomenon of cryptic species complexes. Such complexes are informative models for research into the evolutionary processes that govern species compositions of marine fauna. The snapping shrimp genera Alpheus and Synalpheus are known to harbour large numbers of cryptic species; here, I characterize the genetic structure of the Alpheus armillatus species complex in the northern Caribbean, west Atlantic, and Gulf of Mexico using mitochondrial and nuclear sequence data. Over this geographical region, the complex harbours at least three lineages that are probable reproductively isolated species; all major lineages diverged subsequent to the close of the Isthmus of Panama. Only one lineage was present in the Gulf of Mexico, whereas outside the Gulf of Mexico there was no clear tendency for lineage dominance by geographical region, as most sites were populated by shrimp from at least two lineages. However, within each lineage, there was strong evidence of population genetic differentiation between geographical regions. All lineages showed strong signals of demographic expansion, and one lineage showed sharply reduced genetic diversity, suggestive of past population bottlenecks or recently founded populations with low gene flow from other sites. These results show that evolutionary processes leading to divergence and speciation have been common and recent in the snapping shrimp, and suggest that connectivity among shrimp populations may be limited.

Effect of floral and extrafloral resources on predation of Aphis spiraecola by Harmonia axyridis on Apple - Blaine Spellman; M. W. Brown; Clarissa R. Mathews (BioControl, 2006)

Long Term Effects of Ketogenic Diet in Obese Subjects with High Cholesterol Level - Hussein M. Dashti; Naji S. Al-Zaid; Thazhumpal C. Mathew; Mahdi Al-Mousawi; Hussain Talib; Sami K. Asfar; Abdulla I. Behbahani (Molecular and Cellular Biochemistry, 2006)

Modeling Ocean Ecosystems: The PARADIGM Program - Lewis Rothstein; John Cullen; Mark Abbott; Eric Chassignet; Ken Denman; Scott Doney; Hugh Ducklow; Katja Fennel; Mick Follows; Dale Haidvogel; Eileen Hofmann; David Karl; et al. (Oceanography, 2006)

Antibody-based therapeutics: Focus on prostate cancer - Jeffrey S. Ross; Karen E. Gray; Iain J. Webb; Gary S. Gray; Mark Rolfe; David P. Schenkein; David M. Nanus; Mathew I. Millowsky; Neil H. Bander (Cancer and Metastasis Reviews, 2005)

Hydrography and water masses in the southeastern Arabian Sea during March–June 2003 - S. S. C. Shenoi; D. Shankar; G. S. Michael; J. Kurian; K. K. Varma; M. R. Ramesh Kumar; A. M. Almeida; A. S. Unnikrishnan; W. Fernandes; N. Barreto; C. Gnanaseelan; R. Mathew; et al. (Journal of Earth System Science, 2005)

Application of a quartz crystal microbalance to evaluate biodegradability of starch by Bacillus subtilis - M. Jenkins; M. Horsfall; D. Mathew; M. Scanlon; R. Jayasekara; G.T. Lonergan (Biotechnology Letters, 2004)

Effect of time and mode of application of potassium on the growth, yield and quality of sugarcane ratoon - Thomas Mathew; T. M. Kurian; Babu George; Sosamma Cherian; Jessy M. Kuriakose; K. Sreekumar; G. Jayakumar (Sugar Tech, 2004)

SNTG1, the gene encoding ?1-syntrophin: a candidate gene for idiopathic scoliosis - Stavros Bashiardes; Rose Veile; Missy Allen; Carol A. Wise; Mathew Dobbs; Jose A. Morcuende; Lazlos Szappanos; John A. Herring; Anne M. Bowcock; Michael Lovett (Human Genetics, 2004)

Serum changes in trace elements during thyroid cancers - H. Al-Sayer; T.C. Mathew; S. Asfar; M. Khourshed; A. Al-Bader; A. Behbehani; H. Dashti (Molecular and Cellular Biochemistry, 2004)

Reply to Discussion on ?Dissolution channels in quartz and the role of pressure changes in gold and sulfide deposition in the Archean, greenstone-hosted, Hutti gold deposit, Karnataka, India? by Kolb J, Rogers A and Meyer FM - Hari Shankar Pandalai; Gajanan Narayanrao Jadhav; Biju Mathew; V. Panchapakesan; K.K. Raju; M. L. Patil (Mineralium Deposita, 2004)

Residual effects of sulphur nutrition on the ratoon crop of sugarcane - Thomas Mathew; T. M. Kurian; Sosamma Cherian; G. Jayakumar (Sugar Tech, 2003)

Dissolution channels in quartz and the role of pressure changes in gold and sulfide deposition in the Archean, greenstone-hosted, Hutti gold deposit, Karnataka, India - Hari Shankar Pandalai; Gajanan Narayanrao Jadhav; Biju Mathew; V. Panchapakesan; K. Krishnam Raju; M. L. Patil (Mineralium Deposita, 2003)

Bacterial diversity patterns along a gradient of primary productivity - M. Claire Horner‐Devine; Mathew A. Leibold; Val H. Smith; Brendan J. M. Bohannan (Ecology Letters, 2003)
Primary productivity is a key determinant of biodiversity patterns in plants and animals but has not previously been shown to affect bacterial diversity. We examined the relationship between productivity and bacterial richness in aquatic mesocosms designed to mimic small ponds. We observed that productivity could influence the composition and richness of bacterial communities. We showed that, even within the same system, different bacterial taxonomic groups could exhibit different responses to changes in productivity. The richness of members of the Cytophaga‐Flavobacteria‐Bacteroides group exhibited a significant hump‐shaped relationship with productivity, as is often observed for plant and animal richness in aquatic systems. In contrast, we observed a significant U‐shaped relationship between richness and productivity for α ‐proteobacteria and no discernable relationship for β ‐proteobacteria. We show, for the first time, that bacterial diversity varies along a gradient of primary productivity and thus make an important step towards understanding processes responsible for the maintenance of bacterial biodiversity.

Inward and outward potassium currents through the same chimeric human Kv channel - Anurag Varshney; M. K. Mathew (European Biophysics Journal, 2003)

Speciation of Heavy Metals in Bed Sediments of Wetlands in Urban Coimbatore, India - M. Mathew; R. Mohanraj; P. A. Azeez; S. Pattabhi (Bulletin of Environmental Contamination and Toxicology, 2003)

Modulation of voltage sensitivity by N-terminal cytoplasmic residues in human Kv1.2 channels - Anurag Varshney; Kavitha S.; Mathew M. (European Biophysics Journal, 2002)

Genetic, ecological, and behavioural divergence between two sibling snapping shrimp species (Crustacea: Decapoda: Alpheus ) - L. M. Mathews; C. D. Schubart; J. E. Neigel; D. L. Felder (Molecular Ecology, 2002)
Examination of genetic and ecological relationships within sibling species complexes can provide insights into species diversity and speciation processes. Alpheus angulatus and A. armillatus , two snapping shrimp species with overlapping ranges in the north‐western Atlantic, are similar in morphology, exploit similar ecological niches and appear to represent recently diverged sibling species. We examined phylogenetic and ecological relationships between these two species with: (i) sequence data from two mitochondrial genes (16 S rRNA and COI ); (ii) data on potential differences in microhabitat distribution for A. armillatus and A. angulatus ; and (iii) data from laboratory experiments on the level of reproductive isolation between the two species. DNA sequence data suggest A. armillatus and A. angulatus are sister species that diverged subsequent to the close of the Isthmus of Panama, and that haplotype diversity is lower in A. armillatus than in A. angulatus . Both species are distantly related to A. heterochaelis and A. estuariensis , two species with which A. angulatus shares some similarities in coloration. Ecological data on the distribution of A. angulatus and A. armillatus from two locations revealed differences in distribution of the two species between habitat patches, with each patch dominated by one or the other species. However, there was no apparent difference in distribution of the two species within habitat patches with respect to microhabitat location. Ecological data also revealed that heterospecific individuals often occur in close proximity (i.e. within metres or centimetres) where sympatric. Behavioural data indicated that these species are reproductively isolated, which is consistent with speciation in transient allopatry followed by post‐divergence secondary contact. Our data further resolve taxonomic confusion between the sibling species, A. armillatus and A. angulatus , and suggest that sympatry in areas of range overlap and exploitation of similar ecological niches by these two recently diverged species have selected for high levels of behavioural incompatibility.

Sediment Quality of Wetlands in Coimbatore, Tamilnadu, India - M. Mathew; M. Sathish Kumar; P. A. Azeez; R. Sivakumar; S. Pattabi (Bulletin of Environmental Contamination and Toxicology, 2002)

Response of Avian Communities to Historic Habitat Change in the Northern Chihuahuan Desert - A. M. Pidgeon; N. E. Mathews; R. Benoit; E. V. Nordheim (Conservation Biology, 2001)
Throughout much of the northern Chihuahuan Desert, the grasslands that were widespread at the time of European settlement have been replaced by desert shrublands. Little is known about the effects of this change on avian communities. We analyzed historic U.S. Government Land Office records to assess large‐scale changes in vegetation cover from the 1880s to the present day. We studied vegetation and avian communities in one grassland habitat type and four desert shrubland habitat types to examine (1) how breeding‐bird communities may have changed in response to habitat conversion from grassland to desert shrubland and (2) whether breeding‐bird communities differ among the four desert shrubland habitat types that compose Chihuahuan Desert scrub in this region. To estimate the characteristics of 1880s black grama ( Bouteloua eriopoda ) grassland, we focused on plots located within extensive patches of present‐day black grama and compared the avian communities found there with those in desert shrubland. Species richness was higher in desert shrubland than grassland. Among the desert shrubland habitat types, species richness was consistently highest in mesquite. Avian abundance patterns differed among the four desert shrubland habitat types. At least 30% of the avian community in each habitat pair was distinct. Conversion of grassland to shrubland in south‐central New Mexico has likely been accompanied by a major turnover in the avian community. Remaining tracts of black grama provide habitat for species that may be uniquely adapted to the northern Chihuahuan Desert and should be protected.

Mitochondrial phylogeography, subspecific taxonomy, and conservation genetics of sandhill cranes (Grus canadensis; Aves: Gruidae) - Judith M. Phymer; Mathew G. Fain; Jane E. Austin; Douglas H. Johnson; Carey Krajewski (Conservation Genetics, 2001)

Blood lipids of young distance runners: distribution and inter-relationships among training volume, peak oxygen consumption, and body fatness - Joey C. Eisenmann; Christopher J. Womack; Mathew J. Reeves; James M. Pivarnik; Robert M. Malina (European Journal of Applied Physiology, 2001)

Optimisation of the dehydrogenase assay for measurement of indigenous microbial activity in beach sediments contaminated with petroleum - M. Mathew; J.P. Obbard (Biotechnology Letters, 2001)

Plant tolerance and resistance in food webs: community-level predictions and evolutionary implications - Jonathan M. Chase; Mathew A. Leibold; Ellen Simms (Evolutionary Ecology, 2000)

Molecular cloning of transmembrane and soluble forms of a novel rat natural killer cell receptor related to 2B4 - P. R. Kumaresan; S. E. Stepp; M. Bennett; V. Kumar; P. A. Mathew (Immunogenetics, 2000)

Analysis of single-nucleotide polymorphisms in the interleukin-4 receptor gene for association with inflammatory bowel disease - M. Olavesen; J. Hampe; M. M. Mirza; R. Saiz; C. M. Lewis; S. Bridger; D. Teare; D. F. Easton; T. Herrmann; G. Scott; J. Hirst; J. Sanderson; et al. (Immunogenetics, 2000)

Components of yield and quality in intraspecific hybrids ofSaccharum officinarum L. selected for ancillary uses - N. V. Nair; R. Nagarajan; M. D. Mathew; T. V. Sreenivasan (Sugar Tech, 1999)

Molecular Characterization of an Isolate of Citrus Tristeza Virus that Causes Severe Symptoms in Sweet Orange - Zhong-Nan Yang; Deborah M. Mathews; J. Allan Dodds; T. Erik Mirkov (Virus Genes, 1999)

Embryonic stem cells can be used to construct hybrid cell lines containing a single, selectable murine chromosome - Petra M. Jakobs; Lesley Smith; Mathew Thayer; Markus Grompe (Mammalian Genome, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Selenium and Liver Cirrhosis - A. Al-Bader; H. Abul; T. Hussain; M. Al-Moosawi; T.C. Mathew; H. Dashti (Molecular and Cellular Biochemistry, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Influence of antiestrogens on the migration of breast cancer cells using an in vitro wound model - Annie C. Mathew; Talitha T. Rajah; Gina M. Hurt; S. M. Abbas Abidi; John J. Dmytryk; J. Thomas Pento (Clinical & Experimental Metastasis, 1997)

Wood preservative leachates from docks in an estuarine environment - P. H. Wendt; R. F. Van Dolah; M. Y. Bobo; T. D. Mathews; M. V. Levisen (Archives of Environmental Contamination and Toxicology, 1996)

Wood Preservative Leachates from Docks in an Estuarine Environment - P. H. Wendt; R. F. Van Dolah; M. Y. Bobo; T. D. Mathews; M. V. Levisen (Archives of Environmental Contamination and Toxicology, 1996)

Nucleotide and deduced amino acid sequence of the 3? end of the BYMV-MI genome - A. Mathews; G. Dwyer; S. Wylie; M. G. K. Jones (Archives of Virology, 1995)

Characterization of cell surface material removed by water and NaCl washing ofParacoccus denitrificans grown under conditions of divalent cation deficiency and sufficiency - Sechan Wee; Janet M. Dowding; Mathew J. Nadakavukaren; Brian J. Wilkinson (Antonie van Leeuwenhoek, 1994)

A lymphocyte cell line that makes serum cholinesterase instead of acetylcholinesterase - H. M. Rubinstein; T. Lubrano; H. L. Mathews; C. F. Lange; S. Silberman; E. M. Adams; J. Minowada (Biochemical Genetics, 1984)

The function of the carotenoid pigments of sarcina lutea - Micheline M. Mathews; W. R. Sistrom (Archives of Microbiology, 1960)